Resin film and method for manufacturing the same, and metalized resin film, printed circuit board
Patent Information
- Application Number
- CN202280033445.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-12
- Filing Date
- 2022-04-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-04-27
AI Technical Summary
[0019]根据本发明的一实施方式,可以提供:示出优异的耐焊接热性能、能应对狭间距的电路形成的材料和其方法、具体而言能形成示出优异的耐焊接热性能和对低粗糙度的表面示出强的密合性的化学镀层的树脂薄膜和其制造方法、由树脂薄膜得到的金属化树脂薄膜和印刷电路板。
Smart Images

Figure BDA0004533946600000341 
Figure BDA0004533946600000351 
Figure BDA0004533946600000361
Abstract
Description
Technical Field
[0001] This invention relates to resin films and methods for manufacturing the same, as well as metallized resin films and printed circuit boards. Background Technology
[0002] Printed circuit boards (PCBs) with circuits formed by metal conductors on an insulating substrate are widely used to mount various electronic components and embody the functions of electronic devices. With the increasing functionality, performance, and miniaturization of electronic devices, there is a growing demand for PCBs with narrower pitch circuitry. Specifically, there is a need for PCBs that can be bent into smaller, more compact forms within the electronic device, such as (a) flexible PCBs, (b) rigid-flex PCBs, (c) multilayer flexible PCBs, and (d) COF (chip-on-film) PCBs, which have narrowly pitched circuitry on the flexible film portion.
[0003] As a method for forming circuits with narrow pitch, Patent Document 1 discloses a method for bonding a copper foil with a carrier film to a polyimide sheet.
[0004] In addition, Patent Document 2 discloses the following method: forming a metal layer on a polyimide film using physical vapor deposition methods such as vacuum evaporation, sputtering, and ion plating.
[0005] In addition, Patent Document 3 discloses the following example: copper is directly plated by chemical plating on a material containing a polyimide resin with an organosilicon structure and fumed silica.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent Application Publication No. 2005-76091
[0009] Patent Document 2: Japanese Patent No. 6706013
[0010] Patent Document 3: Japanese Patent No. 5037168 Summary of the Invention
[0011] The problem the invention aims to solve
[0012] However, the aforementioned existing technologies are insufficient from the viewpoint of weldability and sealing performance, and there is room for further improvement.
[0013] One embodiment of the present invention was made in view of the aforementioned problems, and its object is to provide: a novel resin film with excellent solderability and adhesion, a method for manufacturing the same, and a metallized resin film and a printed circuit board obtained from the resin film.
[0014] Solution for solving the problem
[0015] The inventors conducted in-depth research and found that the above-mentioned problems can be overcome.
[0016] In one embodiment of the present invention, a layer A comprising polyimide resin and fumed metal oxide is formed on at least one side of a heat-resistant resin film having a coefficient of linear expansion of 20 ppm / °C or less. The coefficient of linear expansion of the polyimide resin is 30 ppm / °C or more and 100 ppm / °C or less.
[0017] In addition, a method for manufacturing a resin film according to an embodiment of the present invention is as follows: the resin film has a layer A comprising polyimide resin and fumed metal oxide formed on at least one side of a layer B, which is a heat-resistant resin film with a coefficient of linear expansion of 20 ppm / °C or less. The aforementioned polyimide resin has a coefficient of linear expansion of 30 ppm / °C or more and 100 ppm / °C or less. The layer A comprising polyimide resin and fumed metal oxide is obtained by mixing a polyamic acid solution, which is a precursor of polyimide resin, with a fumed metal oxide, and imidizing the resulting fumed metal oxide-dispersed polyamic acid solution.
[0018] The effects of the invention
[0019] According to one embodiment of the present invention, it is possible to provide: a material and method thereof exhibiting excellent resistance to soldering heat and capable of forming narrow-pitch circuits; specifically, a resin film and method thereof capable of forming a chemical plating layer exhibiting excellent resistance to soldering heat and strong adhesion to surfaces with low roughness; a metallized resin film and a printed circuit board obtained from the resin film. Detailed Implementation
[0020] [Technical concept of one embodiment of the present invention]
[0021] The inventors conducted in-depth research and found that the technologies described in the prior art documents 1 to 3 above have the following potential for improvement or problems.
[0022] For example, in Patent Document 1, in order to ensure the tightness of the insulating substrate and the copper foil, unevenness is deliberately formed on the surface of the copper foil. Therefore, in Patent Document 1, it can be said that the thickness of the copper layer is usually thinner than the limit of the copper foil, the etching process has an adverse effect on the circuit shape, there is a limit to the narrowing of the pitch, and in addition, there is an adverse effect on the transmission characteristics.
[0023] Furthermore, in the technology of Patent Document 2, metals such as nickel, chromium, vanadium, titanium, and molybdenum are formed on the surface of a substrate by physical vapor deposition. However, according to the technology of Patent Document 2, when etching with only copper etching solution during circuit formation, metals such as nickel, chromium, and titanium cannot be completely removed. In order to completely remove them, other etching solutions are required, which presents a problem of process complexity.
[0024] Furthermore, although Patent Document 3 discloses a resin film that can form a chemical plating layer on a surface with low roughness, there is room for improvement in aspects such as weldability.
[0025] This invention was made in view of the aforementioned problems, and its object is to provide: a novel resin film with excellent solderability and adhesion, a method for manufacturing the same, and a metallized resin film and a printed circuit board obtained from the resin film. One embodiment of the invention aims, for example, to provide: a material (resin film) and method thereof exhibiting excellent solderability and thermal resistance, capable of forming circuits with narrow pitch; specifically, a resin film and method thereof capable of forming a metallized coating exhibiting excellent solderability and thermal resistance and strong adhesion to surfaces with low roughness. Furthermore, another embodiment of the invention aims to provide: a metallized resin film and a printed circuit board obtained from the resin film.
[0026] [Resin film]
[0027] The resin film of one embodiment of the present invention is characterized in that a layer A comprising polyimide resin and fumed metal oxide is formed on at least one side of a layer B, which is a heat-resistant resin film with a coefficient of linear expansion of 20 ppm / °C or less, wherein the coefficient of linear expansion of the aforementioned polyimide resin is 30 ppm / °C or more and 100 ppm / °C or less.
[0028] The resin film of one embodiment of the present invention, by having the aforementioned structure, possesses the advantages of excellent weldability and adhesion. As an example, in this specification, adhesion is evaluated by peel strength (N / cm), and weldability is evaluated by resistance to moisture-absorbing welding heat.
[0029] Layer A (sometimes referred to as layer A) which contains polyimide resin and fumed metal oxide is described.
[0030] <Layer A (Layer A) comprising polyimide resin and fumed metal oxide>
[0031] A key technical feature of layer A in one embodiment of the present invention is that it comprises a polyimide resin and a fumed metal oxide. Furthermore, by forming this configuration, the adhesion between the resin film and the electroless metallized layer can be significantly improved, and the adhesion immediately after the electroless metallized layer is formed can be significantly improved without the need for heating or similar processes. The mechanism by which this adhesion is achieved is described below.
[0032] The electroless metal plating process consists of multiple independent chemical solution baths. These chemical solution baths are managed under specified conditions (concentration, temperature, etc.), and the surface of the object to be plated is contacted with these chemical solutions for a specified time by methods such as immersion or spraying. Chemical changes occur on the same surface, and physical shape changes occur depending on the circumstances. These chemical solutions contain various components, and the pH varies depending on the type of chemical solution; some solutions exhibit strong alkalinity or strong acidity. On the other hand, it is believed that the polyimide resin and fumed metal oxide, necessary for one embodiment of the present invention, both interact with these chemical solutions, resulting in changes in chemical structure and physical shape, thus affecting the adhesion to the electroless metal plating. Both the fumed metal oxide and the polyimide resin undergo chemical changes in an alkaline environment. For example, the fumed metal oxide dissolves in an alkaline environment, generating ionic metal oxides. For example, the polyimide resin generates ionic amide acid groups through the cleavage reaction of the imide ring in an alkaline environment. These ionic compounds (ionic metal oxides and amide acid groups, etc., exhibiting ionicity) react with metal ions in the electroless metal plating bath, potentially forming a compound at the interface between the polyimide resin and the metal coating that originates from three components: "gas-phase metal oxide," "metal (e.g., copper)," and "polyimide resin." This compound contributes to adhesion, resulting in a perceived increase in the adhesion between the polyimide resin and the metal coating.
[0033] On the other hand, it is believed that the dissolution rates of polyimide resin and fumed metal oxide in an alkaline environment are influenced by the chemical structure and aggregation structure of the polyimide resin, and the chemical structure and specific surface area of the fumed metal oxide, respectively. When layer A, comprising polyimide resin and fumed metal oxide, of one embodiment of the present invention is exposed to an alkaline environment, dissolution occurs corresponding to the dissolution rates of each polyimide resin and fumed metal oxide. Layer A of one embodiment of the present invention has a structure in which the fumed metal oxide exists in a state of being embedded in the polyimide resin phase. Therefore, when layer A of one embodiment of the present invention is exposed to an alkaline environment, fine irregularities of the same degree as the particle size of the fumed metal oxide are generated on the surface of layer A according to the dissolution rates of the alkaline reagents for each of the polyimide resin and fumed metal oxide, resulting in an increase in the surface area of layer A. It is believed that this increase in the surface area of layer A also contributes to the improvement of the adhesion strength.
[0034] Furthermore, the fumed metal oxide required in one embodiment of the present invention has a structure formed by primary particle aggregation, existing in a state of being embedded in the polyimide resin phase. It is also believed that, in one embodiment of the present invention, a portion of a structural unit of the fumed metal oxide is exposed on the surface and / or exists near the surface, while other portions exist along the main direction, thereby ensuring a strong bond between the two and contributing to improved adhesion strength. That is, it is believed that (i) the increased area of the interface between the aforementioned three components—"fumed metal oxide," "metal (e.g., copper)," and "polyimide resin"—and (ii) the fumed metal oxide being embedded in the polyimide resin phase and firmly bonded contribute to increased adhesion strength with the electroless plating metal. It should be noted that the present invention is not limited in any way by the above-mentioned considerations (speculations) concerning the mechanism of adhesion.
[0035] <Layer A of polyimide resin>
[0036] Next, the polyimide resin used in layer A will be described. The polyimide resin is characterized by containing imide groups in its chemical backbone. It is believed that these imide groups (functional groups) in the polyimide resin interact with gaseous metal oxides and metal elements (e.g., copper) to improve adhesion to the electroless metal plating layer. Therefore, in order to achieve the desired adhesion as an embodiment of the present invention, the essential technical feature of the polyimide resin is the inclusion of imide groups. On the other hand, during in-depth research, the inventors independently discovered that the coefficient of linear expansion of the polyimide resin used in layer A affects the adhesion; specifically, a coefficient of linear expansion of 30 ppm / °C or higher indicates good adhesion, leading to the conception of an embodiment of the present invention. In this specification, the coefficient of linear expansion of the polyimide resin is the coefficient of linear expansion in the planar direction when the polyimide resin used in layer A is in the form of a thin film, reflecting the degree of in-plane orientation of the polyimide molecular chains within layer A. The smaller the coefficient of linear expansion of polyimide resin, the more the polyimide molecular chains are oriented along the planar direction; conversely, the larger the coefficient of linear expansion, the more the polyimide molecular chains are oriented along the thickness direction.
[0037] It is known that the coefficient of linear expansion of polyimide resin can be controlled according to the type of monomer used. To reduce the coefficient of linear expansion of polyimide resin, it is effective to use monomers with rigid chemical structures and increase their composition ratio. By using monomers with rigid chemical structures and increasing their composition ratio, when processed (molded) into a film, the polyimide molecular chains are oriented along the planar direction, further enabling the deposition of the molecular chains along the thickness direction.
[0038] As described above, the inventors independently discovered that when the coefficient of linear expansion of the polyimide resin in layer A is too small, the adhesion between the resin film and the electroless metallized layer decreases. The reason for this is uncertain, but it is speculated as follows: When a polyimide obtained from a monomer mixture using monomers with a rigid chemical structure and an increased proportion of those monomers is exposed to an alkaline chemical solution, the polyimide molecules near the surface are modified into polyamic acid due to the cleavage reaction of the imide rings, forming a state where polyamic acid molecules oriented in the planar direction are deposited along the thickness direction. The cohesive force between polyamic acid molecular chains is weaker than that between polyimide molecular chains. Therefore, when evaluating the adhesion by forming an electroless metallized layer (film) on the surface of a film obtained by exposing the aforementioned polyimide to an alkaline chemical solution, the weakly cohesive polyamic acid molecular chains peel off at the layered interface, resulting in a tendency for the adhesion strength between the film and the plating layer (film) to decrease. It should be noted that the present invention is not limited in any way by the above speculation.
[0039] Conversely, to increase the coefficient of linear expansion of polyimide resin, it is effective to use monomers with a flexible chemical structure and increase their composition ratio. By using monomers with a flexible chemical structure and increasing their composition ratio, when molded into a film, the polyimide molecular chains are oriented not only along the planar direction but also along the thickness direction, that is, they tend to exhibit random orientation.
[0040] As described above, the inventors independently discovered that when the linear expansion coefficient of the polyimide resin in layer A is large (e.g., 30 ppm / °C or higher), the adhesion between the resin film and the electroless metallized layer is enhanced. The reason for this is uncertain, but it is speculated as follows: When a polyimide obtained from a monomer mixture using monomers with a soft chemical structure and an increased proportion of those monomers is exposed to an alkaline chemical solution, the polyimide molecules near the surface are modified into polyamic acid due to the cleavage reaction of the imide rings. However, a large number of covalent bonds in the polymer chains also exist in the thickness direction, thus maintaining a high degree of cohesion between the molecular chains. Therefore, when evaluating the adhesion by forming an electroless metallized film on the surface of the film obtained by exposing the aforementioned polyimide to an alkaline chemical solution, as mentioned above, in the case of polyimides with a small linear expansion coefficient and advanced in-plane molecular orientation, the polyamic acid molecular chains do not peel off into layers. As a result, it is speculated that the adhesion strength with the electroless metallized layer tends to increase. It should be noted that the present invention is not limited in any way by the above speculation.
[0041] Based on the above, for the polyimide resin used in layer A, from the viewpoint that the aggregation force of the polyimide resin itself will not be reduced even if the polyimide resin is exposed to an alkaline chemical solution, it is preferable to a polyimide resin with a tendency to random orientation, that is, a polyimide resin with a tendency to be isotropically molecularly oriented, compared to a polyimide resin with in-plane molecular orientation.
[0042] Regarding polyimide resins, there is a correlation between the degree of in-plane molecular orientation and the coefficient of linear expansion. When the in-plane molecular orientation of a polyimide resin is highly advanced, resulting in a weakening of the peel strength between planar-oriented polymer chains, the coefficient of linear expansion becomes less than 30 ppm / °C. The polyimide resin used in layer A preferably has a random orientation tendency, oriented not only along the planar direction but also along the thickness direction, thereby improving adhesion to the electroless metal plating. The coefficient of linear expansion of the polyimide resin is preferably 30 ppm / °C or higher, more preferably greater than 30 ppm / °C, more preferably 35 ppm / °C or higher, further preferably 40 ppm / °C or higher, even more preferably 45 ppm / °C or higher, and particularly preferably 50 ppm / °C or higher.
[0043] On the other hand, if the coefficient of linear expansion of the polyimide resin in layer A increases, the overall coefficient of linear expansion of the resin film of one embodiment of the present invention, composed of layers A and B, tends to increase as well. When the resin film of one embodiment of the present invention is used for printed circuit boards, if the overall coefficient of linear expansion of the resin film increases, the dimensional accuracy required for the mounting process tends to deteriorate, which is undesirable. Furthermore, during in-depth research, the inventors have independently obtained the following novel insight: by making the coefficient of linear expansion of the polyimide resin below 100 ppm, surprisingly, there is a tendency for excellent heat resistance, such as excellent solderability; in other words, there is a tendency for excellent solderability.
[0044] Therefore, the coefficient of linear expansion of the polyimide resin in layer A is preferably 100 ppm / ℃ or less, more preferably 90 ppm / ℃ or less, more preferably 80 ppm / ℃ or less, more preferably 75 ppm / ℃ or less, even more preferably 70 ppm / ℃ or less, even more preferably 65 ppm / ℃ or less, and particularly preferably 60 ppm / ℃ or less.
[0045] <Heat resistance, glass transition temperature, and elastic modulus at high temperature of polyimide resin in layer A>
[0046] The coefficient of linear expansion of the polyimide resin used in layer A is preferably 30 ppm / ℃ or higher, more preferably greater than 30 ppm / ℃. If the coefficient of linear expansion of the polyimide resin increases, the polyimide resin tends to exhibit thermoplasticity. Thermoplastic resins soften at a certain temperature, and have advantages such as being processable, for example, being able to be hot-pressed with copper foil. From the viewpoint of improving the adhesion to electroless metal plating, which is an objective of one embodiment of the present invention, thermoplasticity is not an essential technical feature.
[0047] On the other hand, when considering the use of the resin film according to one embodiment of the present invention for printed circuit boards, it is preferable that the polyimide resin also withstands the high temperatures of the high-temperature processes in its manufacturing process and the high temperatures during component mounting. Therefore, the polyimide resin used in layer A preferably has a high glass transition temperature and a high elastic modulus at high temperatures, without any particular adverse effects if it is excessively high. Based on the above viewpoints, it is preferable that the glass transition temperature of the polyimide resin, which is an indicator of heat resistance, is as high as possible, for example, preferably 180°C or higher, and more preferably 230°C or higher. Furthermore, in order to exhibit good soldering heat resistance, the polyimide resin used in layer A preferably also has a certain or higher elastic modulus near the melting point of the solder. Specifically, the storage modulus of the polyimide resin contained in layer A at 300°C is preferably 0.2 × 10⁻⁶. 8 Pa or higher, more preferably 0.5 × 10 Pa 8 Pa or higher, further optimized to 0.8 × 10 8 Pa or higher, with 1.0 × 10 Pa being the preferred choice. 8 Pa or above.
[0048] <Solubility of polyimide resin in layer A>
[0049] A resin film according to one embodiment of the present invention can be manufactured using a polyimide resin that is soluble in organic solvents as layer A. Specifically, a dispersion obtained by dissolving the soluble polyimide in an organic solvent and further dispersing a gaseous metal oxide in the resulting solution is coated onto layer B, which is a heat-resistant resin film. Then, layer B is dried to obtain the resin film according to one embodiment of the present invention. However, when using the resin film according to one embodiment of the present invention for printed circuit boards, it is preferable that the polyimide resin used in layer A is non-soluble so that adverse conditions such as resin dissolution do not occur during the manufacturing and mounting processes of the printed circuit board when organic solvents are used. In addition, if the polyimide resin is non-soluble in organic solvents, it is more preferable that it does not swell when exposed to organic solvents. On the other hand, from a reliability point of view, it is more preferable that the polyimide resin of layer A is firmly bonded to layer B, which is a heat-resistant resin film. To improve the adhesion between the polyimide resin of layer A and layer B, it is preferable to imidize the polyimide resin precursor (or solution containing the precursor) of layer A after it comes into contact with layer B.
[0050] From the above, an embodiment of the present invention can be achieved whether the polyimide resin used in layer A is soluble or insoluble, but insoluble polyimide resin is preferred. In other words, the polyimide resin contained in layer A is preferably an insoluble polyimide resin. After contacting the precursor (or solution containing the precursor) of the insoluble polyimide resin with layer B, the precursor is imidized, thereby obtaining a resin film of an embodiment of the present invention having layer A containing an insoluble polyimide resin. This results in a resin film with excellent solvent resistance and excellent adhesion between layer A and layer B, which is preferred.
[0051] The insolubility of polyimide resin is described here. In this specification, insolubility of polyimide resin means that it is generally insoluble in organic solvents used in industrial applications. Specifically, it is preferable that at least 10% by weight of the polyimide resin is insoluble in organic solvents at 20°C to 30°C, and more preferably at least 5% by weight. Examples of organic solvents include alcohols such as methanol, ethanol, and propanol; ketones such as acetone and methyl ethyl ketone; aromatic solvents such as toluene, xylene, cresol, and benzene; ethers such as dioxolane, dioxane, tetrahydrofuran, and diethyl ether; and aprotic polar solvents such as N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and acetonitrile, but these are not the only possibilities.
[0052] <Formulation of polyimide resin in layer A>
[0053] Next, the types of monomers used in the polyimide resin used in layer A and the polymerization methods will be explained.
[0054] The essential technical feature of the polyimide resin used in layer A is that its coefficient of linear expansion is 30 ppm / ℃ or higher and 100 ppm / ℃ or lower. In addition to this, the polyimide resin preferably also has appropriately controlled physical properties such as glass transition temperature, storage modulus at high temperatures, and solubility in organic solvents. As a method for controlling these physical properties within appropriate ranges, the selection of raw materials can be cited. As raw material monomers for polyimide resins, monomers with a flexible backbone and monomers with a rigid backbone are suitable for selection, and by further adjusting the mixing ratio, the desired physical properties can be achieved.
[0055] Examples of diamines with a soft backbone include 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, bis{4-(4-aminophenoxy)phenyl} sulfone, 2,2'-bis{4-(4-aminophenoxy)phenyl}propane, bis{4-(3-aminophenoxy)phenyl} sulfone, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4 '-Diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfide, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 3,4'-diaminodiphenylpropane, 3,3'-diaminodiphenylpropane, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,3'- Diaminodiphenyl sulfone, 4,4'-diaminobenzophenone, 3,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis[ [4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, etc.
[0056] On the other hand, examples of diamines with a rigid skeleton include 1,4-diaminobenzene (p-phenylenediamine), 1,3-diaminobenzene, 1,2-diaminobenzene, benzidine, 3,3'-dichlorobenzidine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)benzidine, 1,5-diaminonaphthalene, 4,4'-diaminobenzoylaniline, 3,4'-diaminobenzoylaniline, 3,3'-diaminobenzoylaniline, etc.
[0057] Among these, from the perspective of controlling thermal properties and being readily available for industrial use, diamines with a soft backbone are preferably selected from the group consisting of 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, bis{4-(4-aminophenoxy)phenyl}sulfone, 2,2'-bis{4-(4-aminophenoxy)phenyl}propane, bis{4-(3-aminophenoxy)phenyl}sulfone, 1,3-bis(3-aminophenoxy)benzene, 3,3'-diaminobenzophenone, and 4,4'-diaminobenzophenone. One or more diamines selected from the group consisting of 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, and 2,2'-bis{4-(4-aminophenoxy)phenyl}propane are particularly preferred. As diamines with a rigid backbone, one or more diamines selected from the group consisting of 1,4-diaminobenzene (p-phenylenediamine), 1,3-diaminobenzene, and 2,2'-dimethylbenzidine are preferred from the perspectives of achieving the effect of fixing the polymer chain in a smaller amount and ease of industrial availability. At least one of 1,4-diaminobenzene (p-phenylenediamine) and 2,2'-dimethylbenzidine is particularly preferred. These diamines can be used alone or in mixtures (combinations) of two or more.
[0058] Examples of tetracarboxylic dianhydrides with a flexible backbone include 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,4'-oxobisphthalic anhydride, 4,4'-oxobisphthalic anhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylidene)phthalic anhydride, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, 2, 2-Bis(3,4-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, p-phenylene bis(triphenylene trioxide monoester anhydride), ethylene bis(triphenylene trioxide monoester anhydride), bisphenol A bis(triphenylene trioxide monoester anhydride), etc.
[0059] On the other hand, examples of tetracarboxylic dianhydrides with a rigid framework include pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, and 3,4,9,10-perylenetetracarboxylic dianhydride.
[0060] From the perspective of controlling thermal properties and being readily available for industrial use, one or more tetracarboxylic dianhydrides with a flexible framework are preferably selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 4,4'-oxophthalic anhydride. Among these, 3,3',4,4'-biphenyltetracarboxylic dianhydride is more preferred, as it can be effectively used to achieve a balanced and desirable combination of various physical properties desired in a preferred embodiment of the present invention, such as adhesion to chemically coated films, elastic modulus at high temperatures, glass transition temperature, and coefficient of linear expansion of the polyimide resin.
[0061] As a tetracarboxylic dianhydride with a rigid backbone, pyromellitic dianhydride is preferred from the perspectives of achieving the effect of fixing polymer chains with a smaller amount and its ease of industrial availability. These tetracarboxylic dianhydrides can be used in mixtures of two or more.
[0062] Regarding the relationship between the adhesion and the chemical structure of the polyimide resin in layer A in one embodiment of the present invention, many aspects are unclear and difficult to explain clearly. Based on experience gained during in-depth research, the inventors have found that combining acid dianhydrides and diamines, which reduce the polarization of the imide rings in the polyimide resin, tends to exhibit good adhesion. Specifically, a combination of at least one of the acid dianhydrides, 4,4'-oxobisphthalic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride, with 2,2'-bis(trifluoromethyl)benzidine as a diamine is effective. Preferred combinations of diamines and acid dianhydrides are not particularly limited. Preferably, a combination is made of one or more diamines selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine, 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, and 2,2'-bis{4-(4-aminophenoxy)phenyl}propane, and at least one of 4,4'-oxobisphthalic dianhydride and 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and further, the gaseous metal oxide is combined with appropriate types and mixing amounts. According to this configuration (combination), the adhesion to the electroless metallized layer according to one embodiment of the present invention can be improved, and in particular, the initial state after the formation of the electroless metallized layer can be significantly improved, which is preferred. It should be noted that, in order to achieve a good balance in the elastic modulus, glass transition temperature, coefficient of linear expansion, etc. at high temperatures, it is also preferable to use other diamines and dianhydrides in combination with the above-mentioned preferred diamines and dianhydrides.
[0063] The polyamic acid, as a precursor to the polyimide of layer A, is obtained by mixing the aforementioned diamine and an acid dianhydride in an organic solvent in a substantially equimolar or approximately equimolar manner, and then reacting them. Any organic solvent can be used as long as it is capable of dissolving the polyamic acid. Preferably, amide solvents are used, such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; at least one of N,N-dimethylformamide and N,N-dimethylacetamide is particularly preferred. The concentration of the solids component of the polyamic acid is not particularly limited; if it is in the range of 5% to 35% by weight, a polyamic acid with sufficient mechanical strength is obtained when forming the polyimide.
[0064] There are no particular restrictions on the order in which the diamine and dianhydride used as raw materials are added. By controlling not only the chemical structure of the diamine and dianhydride used as raw materials, but also their order of addition, the properties of the resulting polyimide can also be controlled.
[0065] Furthermore, when using 1,4-diaminobenzene and pyromellitic dianhydride as raw materials, the polyimide structure obtained by combining the two has low durability against degumming residue liquid. Therefore, it is preferable to adjust the order of addition of 1,4-diaminobenzene and pyromellitic dianhydride to avoid forming a structure in which the two are directly bonded.
[0066] Layer A may also contain resins other than the aforementioned polyimide resin as a resin component. The proportion of polyimide resin in the resin component of Layer A is preferably high. For example, of 100% by weight of the resin component contained in Layer A, polyimide resin is preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and most particularly preferably 95% by weight or more. Of 100% by weight of the resin component contained in Layer A, polyimide resin is most preferably 100% by weight; in other words, Layer A most preferably contains only polyimide resin as a resin component.
[0067] <Vacuum-phase metal oxides>
[0068] In one embodiment of the present invention, the fumed metal oxide used is a metal oxide with silicon dioxide, aluminum oxide, titanium dioxide, etc., as the main components. In this embodiment, the fumed metal oxide is preferably a metal oxide obtained by gas-phase synthesis. In the case of gas-phase synthesis, due to the characteristics of its manufacturing process, the resulting fumed metal oxide has the characteristic of forming structural units from primary particle aggregation. In other words, the fumed metal oxide preferably forms structural units from primary particle aggregation (for example, having an aggregated structure like grape clusters). The fumed metal oxide is mixed with polyimide resin to form layer A in one embodiment of the present invention. The results of various studies by the inventors are as follows: layer A is preferably (i) in which the structural units of the fumed metal oxide are embedded in the polyimide resin in a low-porosity state, (ii) in which the structural units exist throughout the main direction from the surface and / or near the surface of layer A, and (iii) in which the structural units are evenly present and dispersed in layer A. This state is considered effective for achieving the tightness intended for an embodiment of the present invention. It should be noted that, unlike the case of gaseous metal oxides with aggregated structures suitable for use in one embodiment of the present invention, spherical or amorphous metal oxide particles (e.g., colloidal silica) that exist independently as primary particles tend to have weaker adhesion to polyimide resins compared to gaseous metal oxides, and are therefore not preferred.
[0069] It should be noted that layer A only needs to contain polyimide resin and fumed metal oxide. Layer A may also contain spherical or amorphous metal oxide particles that exist independently as primary particles. The less the amount of the aforementioned metal oxide particles in layer A, the better. For example, in layer A, relative to 100 parts by weight of the polyimide resin precursor, the proportion of the aforementioned metal oxide particles is preferably less than 10 parts by weight, more preferably less than 5 parts by weight, more preferably less than 1 part by weight, further preferably less than 0.5 parts by weight, and particularly preferably less than 0.1 parts by weight.
[0070] In the blending of polyimide resin and fumed metal oxide, increasing the blending ratio of fumed metal oxide tends to increase the porosity of layer A. When the porosity of layer A is not excessively high, the adhesion between the polyimide resin and the fumed metal oxide does not decrease, indicating a tendency for layer A itself to have good strength. As a result, there is a tendency for good adhesion to the electroless metal plating, and consequently, a tendency for good adhesion between layer A and layer B. Therefore, in the blending of polyimide resin and fumed metal oxide, it is preferable that the blending ratio of fumed metal oxide is not excessively high. Conversely, in the blending of polyimide resin and fumed metal oxide, decreasing the blending ratio of fumed metal oxide tends to decrease the porosity. When the porosity of layer A is not excessively low, it becomes easier to achieve sufficient adhesion to the electroless metal plating, which is preferable. The rationale is that, since the ratio of gaseous metal oxides is not excessively low, the amount of compounds derived from the three components—"gaseous metal oxides," "metals (e.g., copper)," and "polyimide resins"—is sufficient. It should be noted that the present invention is not limited to these assumptions.
[0071] Therefore, in order to achieve good adhesion, it is preferable to control the mixing ratio of polyimide resin and fumed metal oxide within an appropriate range. On the other hand, fumed metal oxides have various grades with different primary particle sizes, structures formed by primary particle aggregation, and surface treatment materials, and it is believed that there exists an appropriate mixing ratio that also affects these factors.
[0072] <Primary particle size and specific surface area of fumed metal oxides>
[0073] In the chemical solution of the electroless metal plating process, a portion of the fumed metal oxide near the surface dissolves, but preferably even if dissolved, the surface roughness of layer A does not increase excessively. Therefore, the primary particle size of the fumed metal oxide is preferably small, specifically, preferably 5 nanometers or more and 1000 nanometers or less, more preferably 5 nanometers or more and 100 nanometers or less, further preferably 5 nanometers or more and 50 nanometers or less, and even more preferably 10 nanometers or more and 20 nanometers or less. Furthermore, the specific surface area of the fumed metal oxide is also a physical property reflecting the primary particle size; the larger the primary particle size, the smaller the specific surface area. The specific surface area of the fumed metal oxide is preferably 30 m² / g or more and 400 m² / g or less, more preferably 100 m² / g or more and 250 m² / g or less.
[0074] <Apparent specific gravity of fumed metal oxides>
[0075] Gas-phase metal oxides are structures formed by the aggregation of particles of a single size. Apparent specific gravity can be used as an indicator of the structural state of gas-phase metal oxides. A low apparent specific gravity indicates a bulky structure, meaning large porosity. Conversely, a high apparent specific gravity indicates a low-volume structure, meaning small porosity.
[0076] Layer A with low porosity can be produced by filling the pores of the structure formed by the aggregation of primary particle size of fumed metal oxides with polyimide resin components. The lower the apparent specific gravity of the fumed metal oxide, the more pores the fumed metal oxide structure has, and by using more polyimide resin components, these pores can be filled. The higher the apparent specific gravity of the fumed metal oxide, the more pores the fumed metal oxide structure can be filled even with a small amount of polyimide resin components. Conversely, when fumed metal oxides are mixed into a constant amount of polyimide resin to produce layer A with low porosity, (i) in the case of fumed metal oxides with low apparent specific gravity, the upper limit of the amount of fumed metal oxides mixed becomes lower, and conversely (ii) in the case of fumed metal oxides with high apparent specific gravity, a large amount of fumed metal oxides can be mixed, that is, the upper limit of the amount of fumed metal oxides mixed becomes higher. As described above, there is no concern about excessive pores being generated in layer A when the amount of fumed metal oxides mixed is not excessive. As a result, the adhesion between the polyimide resin and the fumed metal oxide does not decrease, indicating a tendency for layer A itself to have good strength. Consequently, there is a tendency for good adhesion to the electroless metal plating, and also a tendency for good adhesion between layer A and layer B. Therefore, in the blending of polyimide resin and fumed metal oxide, the blending ratio of fumed metal oxide is preferably not excessively high. Conversely, when the ratio of fumed metal oxide is not excessively low, sufficient adhesion to the electroless metal plating is easily achieved. That is, in the blending of polyimide resin and fumed metal oxide, blending the fumed metal oxide at near the upper limit of the blending amount is effective in achieving good adhesion.
[0077] The upper limit of the amount of fumed metal oxide used to form layer A with low porosity relative to a constant amount of polyimide resin varies depending on the apparent specific gravity of the fumed metal oxide and the surface treatment material. That is, by adjusting the amount of fumed metal oxide relative to a constant amount of polyimide resin according to the apparent specific gravity of the fumed metal oxide and the surface treatment material, the adhesion can be further improved. In one embodiment of the present invention, the apparent specific gravity of the fumed metal oxide is preferably 20 g / L or more and 250 g / L or less, more preferably 20 g / L or more and 220 g / L or less. Furthermore, the higher the apparent specific gravity of the fumed metal oxide, the higher the upper limit of the amount of fumed metal oxide can be, and the adhesion tends to be further improved. Therefore, the apparent specific gravity of the fumed metal oxide is more preferably greater than 50 g / L and less than 250 g / L, more preferably greater than 60 g / L and less than 250 g / L, further preferably greater than 70 g / L and less than 250 g / L, and even more preferably greater than 70 g / L and less than 220 g / L. It should be noted that the apparent specific gravity of the fumed metal oxide can also vary depending on the structural modification of the fumed metal oxide based on mechanically applying shear stress.
[0078] Various surface treatments can be applied to fumed metal oxides. Surface states of fumed metal oxides include silanol (untreated), dimethylsilyl, octylsilyl, trimethylsilyl, dimethylsiloxane, dimethylpolysiloxane, aminoalkylsilyl, and methacryloxysilyl, all of which are industrially available. When the polarity of the surface treatment material for the fumed metal oxide is close to that of the polyimide resin component, the upper limit of the amount of fumed metal oxide in the mixture tends to increase. Furthermore, when the fumed metal oxide is untreated, it exhibits excessively good wettability with the alkaline chemical solutions in electroless metal plating processes, thus tending to result in increased solubility of the fumed metal oxide and a greater surface roughness of layer A. Therefore, it is preferable that the surface of the fumed metal oxide undergoes a suitable hydrophobic treatment. It should be noted that the apparent specific gravity of the fumed metal oxide can be determined according to ISO 787 / XI.
[0079] <Specific examples of gaseous metal oxides>
[0080] Hereinafter, specific examples of fumed metal oxides that are preferably used in one embodiment of the present invention will be shown, but are not limited to these. Fumed metal oxides that satisfy various characteristics including apparent specific gravity are more suitable for use in one embodiment of the present invention. Various grades of fumed metal oxides with different primary particle size, specific surface area, surface treatment material, apparent specific gravity, and metal oxide material can be obtained from AEROSIL Corporation, Wacker Asahikasei Silicone Co., Ltd., and Cabot Corporation, and are preferred for use. Fumed metal oxides manufactured by AEROSIL Corporation will be specifically described below as examples. AEROSIL R972, R972CF, R972V, etc., which are substantially equivalent except for apparent specific gravity, are preferred for use, among which R972 (50 g / L) with a high apparent specific gravity is more preferred. Similarly, AEROSIL R974, R9200, VP RS920, etc., which have equivalent apparent specific gravity, are preferred. Among them, AEROSIL R9200 (200 g / L) and AEROSIL VP RS920 (80 g / L or more and 120 g / L or less), which have high apparent specific gravity, are more preferred. In addition, as one of the preferred physical properties of this embodiment of the invention, which is also low in apparent specific gravity (70 g / L or less), AEROSIL NX130, RY200S, R976, NAX50, NX90G, NX90S, RX200, RX300, R812, R812S, etc., manufactured by AEROSIL Corporation of Japan, are preferred. In addition, as a fumed metal oxide manufactured by AEROSIL Corporation of Japan with a high apparent specific gravity of 70 g / L or higher, other preferred options include AEROSIL 200V, AEROIDE TiO2 P90, AEROIDE TiO2 NKT90, OX50, RY50, RY51, AEROIDE TiO2 P25, R8200, RM50, RX50, AEROIDE TiO2 T805, and R7200. It should be noted that AEROSIL VP RS920 was sold under the name "AEROSIL E9200" from November 2021 onwards.
[0081] Furthermore, "AEROSIL" is a registered trademark of Evonik Operations GmbH. Additionally, as a fumed metal oxide, it is synthesized from gas phase, thus, it is preferable to use a fumed metal oxide with a structure formed by primary particle size aggregation.
[0082] Among these fumed metal oxides, fumed silica such as AEROSIL R972, 972V, NX130, R9200, VP RS920, R974, R976, and R8200 are preferred in terms of good surface shape and appropriate surface roughness of layer A formed by dissolution in an alkaline environment.
[0083] <Mixing percentage of fumed metal oxides>
[0084] Layer A, comprising polyimide resin and fumed metal oxide, is preferably an imidized product of a mixture of the precursor of the polyimide resin and the fumed metal oxide (e.g., a fumed metal oxide-dispersed polyamic acid solution described later). Specifically, by mixing the fumed metal oxide with a polyamic acid solution that serves as a precursor of the polyimide resin constituting layer A, a resin film according to an embodiment of the present invention can be obtained by methods such as: (a) coating the obtained mixture onto a heat-resistant film of layer B, drying layer B, and imidizing the mixture; (b) coating the obtained mixture onto a precursor film of layer B, drying the film, and imidizing the mixture; or, (c) co-extruding the obtained mixture with a resin precursor solution of layer B or a resin solution of layer B, drying the resulting extrudate, and imidizing the mixture.
[0085] The preferred proportion of fumed metal oxide is 10 parts by weight or more and 130 parts by weight or less, relative to 100 parts by weight of the polyimide resin precursor in layer A. As mentioned above, the preferred proportion of fumed metal oxide relative to the polyimide precursor (polyimide resin) in layer A can be adjusted to some extent based on the apparent specific gravity of the fumed metal oxide, but factors such as the surface treatment of the fumed metal oxide also play a role, so it cannot be definitively stated. Here, the preferred proportion of fumed metal oxide is described as an indicator.
[0086] When the apparent specific gravity of the fumed metal oxide is 20 g / L or more and 70 g / L or less, the proportion of the fumed metal oxide (relative to the solid component of the polyimide (precursor) resin) relative to 100 parts by weight of the polyimide resin precursor is preferably 15 parts by weight or more and 80 parts by weight or less, more preferably 20 parts by weight or more and 60 parts by weight or less.
[0087] The proportion of the fumed metal oxide in the formulation (relative to 100 parts by weight of the solid component of the polyimide (precursor) resin) when the apparent specific gravity of the fumed metal oxide is 70 g / L or more and 250 g / L or less is preferably 10 parts by weight or more and 130 parts by weight or less, more preferably 15 parts by weight or more and 120 parts by weight or less, and even more preferably 20 parts by weight or more and 100 parts by weight or less when the apparent specific gravity of the fumed metal oxide is 70 g / L or more and 250 g / L or less.
[0088] As mentioned above, the preferred blending ratio is changed according to the apparent specific gravity of the fumed metal oxide. The higher the apparent specific gravity of the fumed metal oxide, the more its blending amount can be increased, and there is a tendency for the preferred blending amount to also increase. Blending the fumed metal oxide within the above range relative to 100 parts by weight of the polyimide resin precursor results in better adhesion strength, especially in the initial state after chemical plating film formation, leading to a stronger adhesion. It should be noted that various fumed metal oxides with different primary particle sizes, specific surface areas, surface treatment materials, apparent specific gravities, and metal oxide materials can also be mixed (combined) and used.
[0089] <Gas-phase metal oxide dispersion of polyamic acid solution>
[0090] To obtain layer A according to one embodiment of the present invention, it is preferable to mix and disperse the precursor solution of the polyimide resin of layer A with a fumed metal oxide to obtain a fumed metal oxide-dispersed polyamic acid solution (hereinafter, sometimes referred to as layer A dispersion). This layer A dispersion is then imidized to obtain layer A. In other words, layer A is preferably an imidized product of the mixture of the polyimide resin precursor and the aforementioned fumed metal oxide. According to this configuration, there is an advantage of increased adhesion between layer A and layer B.
[0091] The steps for obtaining the dispersion of layer A are described in detail below, but one embodiment of the present invention is not limited thereto.
[0092] (1) An organic solvent is added to a fumed metal oxide, and the fumed metal oxide is dispersed in the organic solvent until it forms structural units of a single-phase particle aggregation. Dispersion methods include dispersers, homogenizers, planetary mixers, bead mills, rotary mixers, rollers, kneaders, high-pressure dispersers, ultrasonic equipment, rotary transformers, etc. It should be noted that as long as the effect of one embodiment of the present invention is obtained, the fumed metal oxide may not be dispersed into the aforementioned structural units in the organic solvent. It should be noted that if the fumed metal oxide can be dispersed into the aforementioned structural units, the fumed metal oxide becomes not fixedly present in layer A. In this case, the surface roughness of layer A is small, which is advantageous and preferred for the formation of fine wiring, which is the objective of one embodiment of the present invention. Furthermore, dispersion and pulverization can be performed under conditions that further reduce the number of structural units of the fumed metal oxide. The organic solvent can be the solvent used in the polymerization of polyamic acid, etc., and amide solvents, such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, etc., are preferred, but not limited to these.
[0093] (2) The liquid obtained in (1) above is mixed and stirred with the precursor solution of the polyimide resin of layer A at the desired mixing ratio to obtain a dispersion of layer A. If the gaseous metal oxide has already been dispersed in an organic solvent in the stage (1) above, the liquid obtained in (1) above can be mixed with the precursor solution above and then stirred to obtain a dispersion of layer A. Alternatively, a dispersion of layer A can also be obtained by not only stirring but also using the various dispersion methods described in (1) above.
[0094] The concentration of the final layer A dispersion is not particularly limited, but a concentration and viscosity suitable for the following process are preferred. Organic solvents can be used to adjust the concentration and viscosity of the layer A dispersion. Furthermore, dehydrating agents, catalysts, etc., for imidizing amines or polyamic acids to impart adhesion to layer B, can be added to the layer A dispersion, etc.
[0095] In addition, fillers may be added to the dispersion in layer A to improve various properties of the film, such as sliding properties, thermal conductivity, electrical conductivity, corona resistance, and ring stiffness. Any filler can be used, but preferred examples include silica, titanium dioxide, alumina, silicon nitride, boron nitride, dicalcium phosphate, calcium phosphate, and mica.
[0096] Furthermore, without impairing the overall properties of the obtained resin layer, thermosetting resins such as epoxy resins and phenoxy resins, and thermoplastic resins such as polyetherketones and polyetheretherketones can be used. As a method for adding these resins, any method that allows them to be added to the aforementioned polyamic acid as long as they are soluble in a solvent can be cited. Polyimide is also soluble, but it can also be added to a polyimide solution. Following the above steps, layer A dispersion can be obtained.
[0097] <Layer B>
[0098] In one embodiment of the present invention, layer B of the heat-resistant resin film has layer A formed on one or both sides. From the viewpoint of dimensional stability when the resin film of this embodiment is used in printed circuit board applications, the coefficient of linear expansion of layer B is preferably 20 ppm / °C or less. The resin composition of layer B is not particularly limited, but liquid crystal polymer films, resin films containing reinforcing fibers, resin films containing inorganic fillers, and polyimide are preferred. From the viewpoints of heat resistance, flexibility, and heat resistance, layer B is more preferably a film containing polyimide (or formed from polyimide), and even more preferably a film containing non-thermoplastic polyimide (or formed from non-thermoplastic polyimide).
[0099] It is known that the coefficient of linear expansion of polyimide resin films can be controlled according to the type of monomer used. To reduce the coefficient of linear expansion of polyimide resin films, it is effective to use monomers with rigid chemical structures and increase their composition ratio. By using monomers with rigid chemical structures and increasing their composition ratio, when forming (processing) them into films, polyimide molecular chains can be oriented along the planar direction, and further deposited along the thickness direction. Conversely, to increase the coefficient of linear expansion of polyimide resin films, it is effective to use monomers with flexible chemical structures and increase their composition ratio. By using monomers with flexible chemical structures and increasing their composition ratio, when forming them into films, the polyimide molecular chains are oriented not only along the planar direction but also along the thickness direction, i.e., they tend to exhibit random orientation. When using a non-thermoplastic polyimide film in layer B, there are no particular limitations on the diamine used in the manufacture of the non-thermoplastic polyimide film; the coefficient of linear expansion of the final polyimide film must be below 20 ppm / ℃. Therefore, in the manufacture of non-thermoplastic polyimide films, a suitable combination of rigid diamines and flexible diamines is preferred, depending on the structure of the acid dianhydride.
[0100] Suitable diamines with a rigid structure for use in the manufacture of non-thermoplastic polyimide films include, for example, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-3,3'-dihydroxybiphenyl, 1,4-diaminobenzene, 1,3-diaminobenzene, 4,4'-bis(4-aminophenoxy)biphenyl, and 4,4'-diaminobenzene aniline.
[0101] In the manufacture of non-thermoplastic polyimide films, suitable diamines with a flexible structure include, for example, 4,4'-diaminodiphenyl ether, 2,2-bis{4-(4-aminophenoxy)phenyl}propane, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, and 1,3-bis(3-aminophenoxy)benzene. In the manufacture of non-thermoplastic polyimide films, diamines listed when describing the polyimide resin of layer A may also be suitable.
[0102] When a non-thermoplastic polyimide film is used in layer B, there are no particular limitations on the acid dianhydrides used in the manufacture of the non-thermoplastic polyimide film, but the coefficient of linear expansion of the final polyimide must be below 20 ppm / ℃. Therefore, in the manufacture of non-thermoplastic polyimide films, it is preferable to use an appropriate combination of rigid and flexible acid dianhydrides, depending on the structure of the diamine. Examples of acid dianhydrides with rigid structures suitable for use in the manufacture of non-thermoplastic polyimide films include 3,3',4,4'-biphenyltetracarboxylic acid dianhydride and pyromellitic acid dianhydride. Examples of acid dianhydrides with flexible structures suitable for use in the manufacture of non-thermoplastic polyimide films include 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride and 4,4'-oxophthalic acid dianhydride. The acid dianhydrides listed when describing the polyimide resin of layer A may also be suitable for use in the manufacture of non-thermoplastic polyimide films.
[0103] Polyamic acid, a precursor to polyimide, is obtained by mixing the aforementioned diamine with an acid dianhydride in an organic solvent in a substantially equimolar or approximately equimolar manner, and then reacting them. Any organic solvent can be used as long as it is capable of dissolving polyamic acid. Preferably, amide solvents are used, such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; at least one of N,N-dimethylformamide and N,N-dimethylacetamide is particularly preferred. The concentration of the solids component of the polyamic acid is not particularly limited; if it is in the range of 5% to 35% by weight, a polyamic acid with sufficient mechanical strength is obtained when forming the polyimide.
[0104] There are no particular restrictions on the order in which the diamine and dianhydride used as raw materials are added. By controlling not only the chemical structure of the diamine and dianhydride used as raw materials, but also their order of addition, the properties of the resulting polyimide can be controlled.
[0105] In the aforementioned polyamic acid, fillers may be added to improve various properties of the film, such as lubricity, thermal conductivity, electrical conductivity, corona resistance, and ring stiffness. Any filler can be used, but preferred examples include silica, titanium dioxide, alumina, silicon nitride, boron nitride, dicalcium phosphate, calcium phosphate, and mica.
[0106] Furthermore, without compromising the overall properties of the resulting resin layer, thermosetting resins such as epoxy resins and phenoxy resins, and thermoplastic resins such as polyetherketones and polyetheretherketones can be used. As a method of adding these resins, one can add them to the aforementioned polyamic acid as long as they are soluble in a solvent. The polyimide is also a soluble polyimide, but it can also be added to a polyimide solution. If the polyimide is insoluble in a solvent, one can use a method whereby the aforementioned polyamic acid is first imidized, and then the polyimide obtained by imidization is compounded with a polyimide insoluble in a further added solvent by melt mixing. However, there is a possibility of deterioration in the weld heat resistance and / or heating shrinkage of the resulting flexible metal-coated laminate; therefore, it is desirable that a molten polyimide is not used in one embodiment of the present invention. Therefore, it is desirable to use a soluble resin for mixing with the polyimide.
[0107] The method for obtaining the non-thermoplastic polyimide film preferably used in layer B of an embodiment of the present invention preferably includes the following steps (i) to (iv).
[0108] (i) The process of reacting an aromatic diamine with an aromatic tetracarboxylic acid dianhydride in an organic solvent to obtain a polyamic acid solution;
[0109] (ii) The process of casting a film-forming coating containing the aforementioned polyamic acid solution onto a support;
[0110] (iii) The process of heating the aforementioned film-forming coating on a support and then peeling it off from the support to obtain a gel film;
[0111] (iv) The process of further heating the gel film to imidize the polyamic acid remaining in the gel film and then drying it.
[0112] (ii) and subsequent processes are broadly classified into thermal imidization and chemical imidization. Thermal imidization involves casting a polyamic acid solution as a film-forming coating onto a support, without using dehydrating ring-closing agents, and relying solely on heating to promote imidization. Chemical imidization involves adding at least one of a dehydrating ring-closing agent and a catalyst as imidization accelerators to a polyamic acid solution, using it as a film-forming coating to promote imidization. Any method can be used, but chemical imidization offers superior productivity.
[0113] As a dehydrating ring-closing agent, it is suitable for using acid anhydrides, represented by acetic anhydride. As a catalyst, it is suitable for using tertiary amines such as aliphatic tertiary amines, aromatic tertiary amines, and heterocyclic tertiary amines.
[0114] As a support for cast film coatings, it is suitable to use glass plates, aluminum foil, stainless steel belts, stainless steel drums, etc. Heating conditions are set according to the thickness of the final film and / or the production speed. For film coatings, after either partial imidization or drying, the imide is peeled off from the support to obtain a polyamic acid film (hereinafter referred to as a gel film).
[0115] The ends of the aforementioned gel film are fixed, and the gel film is dried while avoiding shrinkage during curing to remove water, residual solvent, and imidization accelerator from the gel film. In this way, the amyl acid remaining in the gel film is completely imidized, resulting in a film containing polyimide. The heating conditions can be appropriately set according to the thickness of the final film and / or the production speed.
[0116] Furthermore, as an embodiment of the present invention, layer B can preferably be an industrially available polyimide film. Examples of commercially available polyimide films that can be used as layer B include Apical (manufactured by Kaneka), Kapton (manufactured by DU PONT-TORAY CO.,LTD.), and Upilex (manufactured by Ube Industries).
[0117] The resin film of one embodiment of the present invention can be as follows:
[0118] A resin film comprising layer A and layer B,
[0119] Layer A comprises polyimide resin and fumed metal oxide.
[0120] The aforementioned layer B comprises a heat-resistant resin film with a linear expansion coefficient of less than 20 ppm / ℃, or is such a heat-resistant resin film.
[0121] The aforementioned layer A is formed on at least one surface of the aforementioned layer B.
[0122] The linear expansion coefficient of the aforementioned polyimide resin is above 30 ppm / ℃ and below 100 ppm / ℃.
[0123] <Preparation method of resin film comprising layer A and layer B>
[0124] A method for manufacturing a resin film according to an embodiment of the present invention is as follows: the resin film has a layer A comprising polyimide resin and fumed metal oxide formed on at least one side of a layer B, which is a heat-resistant resin film with a coefficient of linear expansion of 20 ppm / ℃ or less. The polyimide resin has a coefficient of linear expansion of 30 ppm / ℃ or more and 100 ppm / ℃ or less. The layer A comprising the polyimide resin and the fumed metal oxide is obtained by mixing a polyamic acid solution, which is a precursor of the polyimide resin, with the fumed metal oxide, and imidizing the resulting fumed metal oxide-dispersed polyamic acid solution.
[0125] The method for manufacturing the resin film according to one embodiment of the present invention can be as follows:
[0126] A method for manufacturing a resin film includes the following steps:
[0127] Step 1: A polyamic acid solution, serving as a precursor to polyimide resin, is mixed with a fumed metal oxide; and,
[0128] Step 2 involves imidizing the gaseous metal oxide-dispersed polyamic acid solution obtained in Step 1.
[0129] The aforementioned resin film comprises the aforementioned layer A and the aforementioned layer B.
[0130] Layer A comprises the aforementioned polyimide resin and the aforementioned fumed metal oxide.
[0131] The aforementioned layer B comprises a heat-resistant resin film with a linear expansion coefficient of less than 20 ppm / ℃, or is such a heat-resistant resin film.
[0132] The aforementioned layer A is formed on at least one surface of the aforementioned layer B.
[0133] The linear expansion coefficient of the aforementioned polyimide resin is above 30 ppm / ℃ and below 100 ppm / ℃.
[0134] Regarding step 1 and the gaseous metal oxide dispersed polyamic acid solution obtained in step 1, the scheme is the same as that described in the aforementioned item "Gas-phase metal oxide dispersed polyamic acid solution," therefore, that record is referenced, and the description is omitted here. The preferred scheme described in the aforementioned item "Gas-phase metal oxide dispersed polyamic acid solution" is also a preferred scheme for step 1 and the gaseous metal oxide dispersed polyamic acid solution obtained in step 1.
[0135] The resin film of one embodiment of the present invention comprises layer A and layer B. Furthermore, the resin film of one embodiment of the present invention is composed of layer A and layer B. Layer B of one embodiment of the present invention must be a heat-resistant resin film with a coefficient of linear expansion of 20 ppm / °C or less. Examples of layer B, i.e., the aforementioned heat-resistant resin film, include liquid crystal polymer films, resin films containing reinforcing fibers, resin films containing inorganic fillers, industrially available polyimide films, and non-thermoplastic polyimide films manufactured through the aforementioned steps (i) to (iv). Preferably, the dispersion of layer A obtained in step 1 is coated (applied) onto the surface of these heat-resistant resin films (layer B), and the dispersion of layer A is dried and imidized to obtain the resin film of one embodiment of the present invention.
[0136] Alternatively, a co-extrusion die with multiple flow paths can be used in step (ii) above to obtain a resin film with multiple layers according to one embodiment of the present invention. Alternatively, layer A dispersion can be coated onto the surface of the gel film obtained in step (iii) above, and both the gel film and layer A can be simultaneously dried and imidized to obtain a resin film according to one embodiment of the present invention. In any case, heating conditions can sometimes affect various film properties and / or adhesion to the electroless metallized layer. Therefore, it is preferable to set appropriate heating temperature and heating time. Furthermore, it is also preferable to set appropriate heating conditions based on the chemical structure, concentration, solvent type, and / or final thickness of the polyamic acid contained in the layer A dispersion, and suitable heating conditions cannot be generalized. For example, it is conceivable that the thickness of layer A is 10 micrometers or less. In this case, it is preferable to perform the following steps (1) to (3) (wherein, (2) is performed as needed) to imide the layer A dispersion, etc.: (1) Dry the layer A dispersion, etc. at a low heating temperature, i.e., at a heating temperature of 100°C or higher and 200°C or lower, for 1 minute or more and 5 minutes or less; (2) Then, as needed, heat the layer A dispersion, etc. at a temperature of 200°C or higher and 300°C or lower; (3) As the final heating condition, heat the layer A dispersion, etc. at a temperature of 300°C or higher and 500°C or lower for 1 minute or more and 5 minutes or less.
[0137] There are roughly two methods for imidization in step 2: thermal imidization and chemical imidization. Imidization of the gas-phase metal oxide dispersed polyamic acid solution (layer A dispersion) is a method that promotes imidization solely by heating without using dehydrating ring-closing agents, etc., and thermal imidization is preferred.
[0138] Layer A functions to bond the electroless metal plating layer. It is envisioned that copper foil is laminated onto layer A to manufacture a copper-clad laminate. In this case, an adhesive layer thickness with surface irregularities that only bond the copper foil is preferred. However, in one embodiment of the present invention, layer A is obtained by depositing the electroless metal plating layer on its surface to form a metal layer. Therefore, even if layer A is relatively thin, it can still exhibit good adhesion to the electroless metal plating layer that originally served its function. From the viewpoint of industrially stable formation of layer A, layer A preferably has a thickness of 0.1 micrometers or more and 30 micrometers or less, and more preferably a thickness of 1 micrometer or more and 10 micrometers or less. On the other hand, when the resin film of one embodiment of the present invention is used in a printed circuit board, it is preferable to appropriately design the coefficient of linear expansion, thereby controlling warpage caused by temperature changes in the composite containing the conductor layer with the electroless metal plating layer. By considering parameters such as the thickness of layer A, the coefficient of linear expansion of layer A alone, the thickness of layer B, and the coefficient of linear expansion of layer B alone, the coefficient of linear expansion of the resin film of one embodiment of the present invention can be controlled. By taking the aforementioned parameters into consideration, it is preferable to perform an operation in which the coefficient of linear expansion of copper, which serves as the conductor layer, is consistent with the coefficient of linear expansion of the resin film of an embodiment of the present invention.
[0139] <Chemical Metal Plating>
[0140] A chemically plated metal layer can be formed on the surface of layer A of the resin film according to one embodiment of the present invention. By forming a chemically plated metal layer on the surface of layer A, a metallized resin film can be obtained. The metallized resin film with a chemically plated metal layer formed on the surface of layer A is also an embodiment of the present invention. The chemically plated metal layer (film) obtained by chemical plating can be thinner than that of ordinary copper foil. The thickness of the aforementioned chemically plated metal layer is preferably 0.01 micrometers to 10.00 micrometers, more preferably 0.10 micrometers to 2.00 micrometers, and even more preferably 0.20 micrometers to 1.00 micrometers.
[0141] In one embodiment of the present invention, electroless metal plating preferably utilizes a reduction process involving chemical reactions. Examples of metals suitable for electroless metal plating include copper, nickel, gold, and silver, all of which can be used in this embodiment. Electroless copper plating and electroless nickel plating are preferred, as electroless copper plating is widely used as a process for making the insulating resin surface of the walls of vias and pathways in printed circuit boards conductive, and is therefore most preferred. In other words, electroless metal plating in one embodiment of the present invention is preferably electroless copper plating. Electroless copper plating processes widely used in printed circuit boards can utilize the chemical solution processes of various chemical solution manufacturers. Furthermore, a desmearing treatment is usually performed before electroless copper plating. This desmearing treatment is performed to remove slag generated on the surface of the copper produced during the via forming process and the laser pathway forming process. The desmearing treatment also imparts a chemical change to the surface of the resin film in this embodiment, and is therefore preferred. The desmearing process and the electroless copper plating process are performed by sequentially treating the substrate with various chemical solutions. For example, the descaling process consists of a chemical solution for swelling, a chemical solution for etching, and a chemical solution for reduction. Similarly, the electroless copper plating process consists of a series of chemical solutions performing various functions, including a cleaning and conditioning chemical solution, a soft etching chemical solution, a pre-impregnation chemical solution, a catalytic chemical solution, an activation chemical solution, and a chemical solution for electroless copper plating. These processes can utilize chemical solution technologies from various plating chemical solution manufacturers. For example, chemical solutions and technologies from companies such as Atotech Limited, Okuno Pharmaceutical Co., Ltd.'s Ad Cupper IW, Uemura Kogyo Co., Ltd.'s Through-cupper PEA, Rohm and Haas Electronic Materials, and Meltex Inc. can be used, and combinations thereof are also suitable. These electroless copper plating processes sometimes contain trace amounts of nickel, but these electroless metals (electroless copper plating) can be used within a range that does not impair the effects of one embodiment of the present invention. It should be noted that when performing electroless plating on layer A, layer A can be electroless plated directly, or it can undergo pretreatment such as alkali treatment or desmearing treatment on layer A before electroless plating can be performed on the pretreated layer A. Examples of alkali solutions used for alkali treatment include sodium hydroxide aqueous solution and potassium hydroxide aqueous solution.
[0142] In one embodiment of the present invention, the objective of obtaining a metallized resin film by performing only a chemical plating metal layer formation process (chemical plating metallization process) on a resin film is to exhibit sufficient adhesion between the resin film and the chemical plating metal. In cases of low adhesion, problems such as circuit peeling off from the resin film substrate may occur in subsequent circuit formation processes. To improve the adhesion between the resin film and the chemical plating metal in a metallized resin film, sometimes the following operation is performed: after the chemical plating process, the metallized resin film is heated, for example, at a temperature of 150°C or higher, thereby improving the adhesion. However, when the metallized resin film is heated, the following issues arise: (a) the process is complex; (b) surface oxidation of the chemical plating metal layer caused by heating can lead to adverse effects and problems in subsequent processes; and (c) even heating does not result in sufficient improvement in adhesion. In one embodiment of the present invention, good adhesion can be obtained without heating the metallized resin film at high temperatures, and it also possesses heat resistance for use as a printed circuit board. In other words, the excellent adhesion of the resin film according to one embodiment of the present invention is at least intended to mean that, for a metallized resin film obtained by forming a chemically plated metal layer on the surface of layer A of the resin film, the peel strength of the chemically plated metal layer in the metallized resin film is excellent (e.g., exhibiting a peel strength of 3 N / cm or more) without subjecting the metallized resin film to heat treatment at 150°C or more. In this specification, the peel strength of the chemically plated metal layer in a metallized resin film obtained by forming a chemically plated metal layer on the surface of layer A of the resin film and without subjecting the metallized resin film to heat treatment at 150°C or more is sometimes referred to as "initial peel strength". In one embodiment of the present invention, it is preferable that, for a metallized resin film obtained by forming a chemically plated metal layer on the surface of layer A of the resin film, the chemically plated metal layer in the metallized resin film exhibits a peel strength of 3 N / cm or more, more preferably 5 N / cm or more, without subjecting the metallized resin film to heat treatment at 150°C or more. In one embodiment of the present invention, the aforementioned metallized resin film preferably exhibits a peel strength of 3 N / cm or more, more preferably 5 N / cm or more, without undergoing heat treatment at 150°C or more after forming the aforementioned chemically plated metal layer.
[0143] Furthermore, when the substrate (resin film) is made conductive by chemical metallization, even if good adhesion is observed when there is no circuit pattern on the back side of the substrate (resin film), sufficient adhesion may not be observed when there is a circuit pattern on the back side of the substrate (resin film). In a preferred embodiment of the present invention, good adhesion can be obtained regardless of the presence or absence of a circuit pattern on the back side without subjecting the metallized resin film to high-temperature heating, and it also has heat resistance for use as a printed circuit board. In other words, the resin film in one embodiment of the present invention is not essential, but for the metallized resin film obtained by forming chemical metallization layers on both sides of layer A of the resin film, it is preferable that the peel strength of the chemical metallization layer in the metallized resin film is excellent (for example, peel strength of 3 N / cm or more) and that the metallized resin film is not subjected to heat treatment of 150°C or higher. In one embodiment of the present invention, for a metallized resin film obtained by forming a chemically plated metal layer on both sides of layer A of a resin film, it is preferable that the chemically plated metal layer in the metallized resin film exhibits a peel strength of 3 N / cm or more, more preferably 5 N / cm or more, without subjecting the metallized resin film to heat treatment at 150°C or more. In another embodiment of the present invention, in the aforementioned metallized resin film, it is preferable that after forming the aforementioned chemically plated metal layer on both sides, it exhibits a peel strength of 3 N / cm or more, more preferably 5 N / cm or more, without subjecting it to heat treatment at 150°C or more.
[0144] Furthermore, in one embodiment of the present invention, for the metallized resin film obtained by forming a chemically plated metal layer on the surface of layer A of the resin film, sufficient adhesion can be obtained even when drying at room temperature without active heating. When the metallized resin film obtained after the chemically plated metal layer formation process is wetted in a cleaning solution such as water, subsequent processes, such as the lamination process of dry film resist, sometimes exhibit defects. Therefore, for the metallized resin film obtained by the chemically plated metal layer formation process, a heat drying process for drying purposes is preferably performed. The heating temperature in the aforementioned heat drying process is preferably 150°C or less, more preferably less than 150°C, and even more preferably 100°C or less. The heating time in the heat drying process is preferably 30 minutes or less, and even more preferably 10 minutes or less. By heating and drying the metallized resin film under stable conditions within the aforementioned range, the oxidation of the chemically plated metal can be suppressed to a practically problem-free level, while also obtaining good adhesion. Therefore, it is preferable to perform a heat drying process on the metallized resin film under stable conditions within the aforementioned range.
[0145] To suppress the peeling of circuit patterns during the circuit formation process in printed circuit board manufacturing, it is preferable that the metallized resin film obtained by chemically plating a metal layer onto the resin film (without heat treatment at 150°C or higher) has sufficient adhesion. The peel strength (initial peel strength) of this metallized resin film is preferably 3 N / cm or more, more preferably 5 N / cm or more, further preferably 6 N / cm or more, and even more preferably 7 N / cm or more.
[0146] Printed Circuit Boards
[0147] Printed circuit boards using the resin film of one embodiment of the present invention, or the metallized resin film of one embodiment of the present invention, are also embodiments of the present invention. Hereinafter, a method for manufacturing a printed circuit board using the resin film of one embodiment of the present invention will be described. The resin film of one embodiment of the present invention can be used as a metallized resin film having a chemically plated copper coating (chemically plated copper layer) firmly bonded to the surface of a low-roughness layer A using a chemically plated metal, particularly a commonly used chemically plated copper solution. By utilizing the resin film or metallized film of one embodiment of the present invention, narrow-pitch circuits can be formed regardless of subtraction or addition methods, and without using complex processes such as button electroplating. Furthermore, by utilizing the resin film or metallized film of one embodiment of the present invention, conductor layers and circuits with narrow pitch and good circuit shape, excellent transmission characteristics, and thin thickness can be obtained. That is, by utilizing the resin film or metallized film of one embodiment of the present invention, printed circuit boards with high flexibility can be manufactured, including flexible printed circuit boards, multilayer flexible printed circuit boards, rigid-flex substrates, and flip-chip thin-film substrates.
[0148] The process of forming a chemically plated metal layer on at least a single surface of the resin film of one embodiment of the present invention can also be combined with circuit formation processes based on known methods such as subtraction and addition methods, multilayering, and stacking multilayering. In the case of multilayering, it can be combined with suitable adhesives and adhesive sheets. In addition, it can also be combined with via formation and blind path formation. For example, for the resin film of one embodiment of the present invention, the following methods (1) to (3) are performed to obtain various printed circuit boards described above: (1) First, vias are formed, and then a chemically plated metal layer formation process is performed to simultaneously form a chemically plated metal layer (film) on the via wall and the surface of the resin film; then, (2) circuit formation is performed using known methods; further (3) multilayering, protective film formation, and surface treatment are performed using known methods. It should be noted that in order to form narrow-pitch circuits, it is preferable that the surface roughness of the resin film of one embodiment of the present invention is small. In one embodiment of the present invention, the surface roughness Ra of the resin film (layer A) exposed by etching to remove the electroless metal plating layer (film) is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less. The aforementioned surface roughness can be adjusted by changing the amount of fumed metal oxide added to the polyimide precursor, the type of fumed metal oxide (apparent specific gravity, surface treatment, etc.), the chemical structure of the polyimide resin in layer A, the descaling conditions, and the conditions for forming the electroless metal plating layer.
[0149] A printed circuit board obtained by an embodiment of the present invention can transmit GHz-band electrical signals by using a resin film or metallized resin film of an embodiment of the present invention. Here, "transmitting GHz-band electrical signals" means that, in a microstrip line transmission path having a signal line with a thickness of 12 micrometers, a resin film of an embodiment of the present invention with a thickness of 25 micrometers, and a ground layer with a thickness of 12 micrometers, and processed with a characteristic impedance of 50Ω, when measuring the insertion loss S21 parameter using a network analyzer E5071C (Keysight Technologies) and a GSG250 probe, the transmission loss is less than 7 dB / 100 mm at 10 GHz, less than 11 dB / 100 mm at 20 GHz, and less than 14 dB / 100 mm at 30 GHz. Here, the 12-micrometer-thick signal line is intended to refer to wiring formed by a conductor layer with a total thickness of 12 micrometers, formed by a chemically plated metal layer and an electrolytically plated copper layer. Furthermore, the 12-micrometer-thick ground layer is intended to refer to a ground layer formed by a conductor layer with a total thickness of 12 micrometers, consisting of a chemically plated metal layer and an electrolytically plated copper layer. Additionally, (i) a film (laminar) sequentially having a signal line with a thickness of 12 micrometers / a resin film with a thickness of 25 micrometers according to an embodiment of the present invention, and (ii) a film (laminar) sequentially having a signal line with a thickness of 12 micrometers / a resin film with a thickness of 25 micrometers / a ground layer with a thickness of 12 micrometers, can also be considered a metallized resin film according to an embodiment of the present invention.
[0150] [1] A resin film, characterized in that a layer A comprising polyimide resin and fumed metal oxide is formed on at least one side of a layer B, which is a heat-resistant resin film with a coefficient of linear expansion of less than 20 ppm / ℃.
[0151] The linear expansion coefficient of the aforementioned polyimide resin is above 30 ppm / ℃ and below 100 ppm / ℃.
[0152] [2] The resin film according to [1] is characterized in that the apparent specific gravity of the aforementioned gaseous metal oxide is more than 20 g / L and less than 220 g / L.
[0153] [3] The resin film according to [1] or [2] is characterized in that the aforementioned fumed metal oxide is in the proportion of 10 to 130 parts by weight relative to 100 parts by weight of the aforementioned polyimide resin precursor.
[0154] [4] The resin film according to any one of [1] to [3] is characterized in that the aforementioned fumed metal oxide is fumed silicon dioxide.
[0155] [5] The resin film according to any one of [1] to [4] is characterized in that layer A, which comprises the aforementioned polyimide resin and the aforementioned fumed metal oxide, is an imide of a mixture of the precursor of the polyimide resin and the aforementioned fumed metal oxide.
[0156] [6] The resin film according to any one of [1] to [5] is characterized in that the storage modulus of the aforementioned polyimide resin at 300°C is 1×10⁻⁶. 8 Pa or above.
[0157] [7] The resin film according to any one of [1] to [6] is characterized in that the aforementioned polyimide resin is a non-soluble polyimide resin.
[0158] [8] The resin film according to any one of [1] to [7] is characterized in that the aforementioned layer B comprises polyimide resin.
[0159] [9] A metallized resin film, wherein a chemically plated metal layer is formed on the surface of the aforementioned layer A of the resin film described in any one of [1] to [8].
[0160]
[10] The metallized resin film according to [9] is characterized in that the aforementioned chemical metal plating is chemical copper plating.
[0161]
[11] The metallized resin film according to [9] or
[10] is characterized in that the surface roughness Ra of the resin film exposed by etching to remove the aforementioned chemically plated metal layer of the aforementioned metallized resin film is less than 200 nanometers.
[0162]
[12] The metallized resin film according to any one of [9] to
[11] is characterized in that, after the aforementioned chemically plated metal layer is formed, the aforementioned metallized resin film exhibits a peel strength of 5 N / cm or more without heat treatment at 150°C or higher.
[0163]
[13] A printed circuit board that uses a resin film as described in any one of [1] to [8] or a metallized resin film as described in any one of [9] to
[12] .
[0164]
[14] The printed circuit board according to
[13] is capable of transmitting electrical signals in the GHz band.
[0165]
[15] A method for manufacturing a resin film, characterized in that a layer A comprising polyimide resin and fumed metal oxide is formed on at least one side of a layer B, which is a heat-resistant resin film with a linear expansion coefficient of less than 20 ppm / ℃.
[0166] The aforementioned polyimide resin has a coefficient of linear expansion of 30 ppm / ℃ or higher and 100 ppm / ℃ or lower.
[0167] The aforementioned layer A, comprising the aforementioned polyimide resin and the aforementioned fumed metal oxide, is obtained by mixing a polyamic acid solution, which is a precursor of the aforementioned polyimide resin, with the aforementioned fumed metal oxide, and then imidizing the resulting fumed metal oxide-dispersed polyamic acid solution.
[0168]
[16] The method for manufacturing a resin film according to
[15] is characterized in that the aforementioned gaseous metal oxide dispersed polyamic acid solution is coated on the aforementioned layer B formed from the aforementioned heat-resistant resin film, and the aforementioned gaseous metal oxide dispersed polyamic acid solution is dried and imidized.
[0169]
[17] The method for manufacturing a resin film according to
[15] is characterized in that the aforementioned gaseous metal oxide dispersed polyamic acid solution and the aforementioned precursor solution of layer B formed from the aforementioned heat-resistant resin film are co-extruded, and the aforementioned gaseous metal oxide dispersed polyamic acid solution and the aforementioned precursor solution are dried and imidized.
[0170] Example
[0171] Hereinafter, an embodiment of the present invention will be further described in detail based on examples and comparative examples. It should be noted that the present invention is not limited to the following embodiments.
[0172] <Fabrication of a single-layer film of polyimide resin in layer A>
[0173] The polyamic acid solution obtained in the synthesis example was coated onto aluminum foil. The polyamic acid solution was then sequentially heated at 120°C for 360 seconds, at 200°C for 60 seconds, at 350°C for 200 seconds, and at 450°C for 30 seconds to induce imidization. Next, the aluminum foil was dissolved and removed using an etching solution to obtain a monolayer film of polyimide resin layer A. The coefficient of linear expansion, storage modulus, glass transition temperature, and solubility of this monolayer film were evaluated.
[0174] <Determination of the coefficient of linear expansion>
[0175] The coefficient of linear expansion was determined using a Seiko Electronics TMA120C. The sample dimensions were set to 3 mm in width and 10 mm in length. For the sample, under a load of 3 g, the temperature was temporarily raised from 10 °C to 400 °C at a rate of 10 °C / min. Then, the sample temperature was cooled to 10 °C, and subsequently raised again at a rate of 10 °C / min. The average value was calculated from the coefficient of thermal expansion at the second temperature rise from 100 °C to 200 °C.
[0176] <Determination of storage modulus and glass transition temperature of layer A>
[0177] The monolayer film obtained in the aforementioned project, "Preparation of a Monolayer Film of Polyimide Resin in Layer A," was used as a sample. The storage modulus and glass transition temperature were measured using a DMS6100 manufactured by Seiko Electronics Co., Ltd. The sample dimensions were set to a width of 9 mm and a length of 50 mm. Measurements were performed at frequencies of 1, 5, and 10 Hz, with a heating rate of 3 °C / min over a temperature range from 20 °C to 400 °C. The storage modulus value was recorded at 300 °C. The glass transition temperature (hereinafter referred to as "Tg") was derived from the inflection point of the storage modulus.
[0178] <Solubility>
[0179] For the monolayer films obtained in the aforementioned project <Preparation of a monolayer film of polyimide resin in layer A>, evaluate their solubility in the following organic solvents. If any organic solvent can dissolve at a concentration of 10% by weight or more, the film is considered soluble and marked as × (poor); if it does not dissolve at a concentration of 10% by weight or more, the film is considered insoluble and marked as ○ (good). The temperature of the organic solvent is set to 25°C.
[0180] Organic solvents: methanol, methyl ethyl ketone, toluene, tetrahydrofuran, N,N-dimethylformamide
[0181] <Evaluation of the fabrication of double-sided copper-clad laminates>
[0182] For the resin films obtained in the examples and comparative examples, under the conditions in Tables 1-3 (Atotech Limited), the resin films were sequentially subjected to desmearing treatment, electroless copper plating, and electrolytic copper plating to obtain a double-sided laminate for evaluation. The thickness of the electrolytic copper plating was set to 12 micrometers.
[0183] [Table 1]
[0184]
[0185] [Table 2]
[0186]
[0187] [Table 3]
[0188]
[0189] <Peel strength>
[0190] In one embodiment of the present invention, the adhesion between the resin film and the electroless metallized layer in the metallized resin film can be achieved as follows:
[0191] (a) The metallized resin film obtained by only performing chemical plating to form a metal layer exhibits sufficient adhesion.
[0192] (b) Exhibits good adhesion at high temperatures without heat treatment of the metallized resin film.
[0193] (c) Good adhesion and performance are achieved regardless of the presence or absence of circuit patterns on the back side of the metallized resin film.
[0194] (d) It has the heat resistance of a printed circuit board, in other words, it has good adhesion even when the metallized resin film is placed at high temperature.
[0195] Therefore, problems such as reduced reliability of the printed circuit board caused by peeling the circuit from the resin film substrate during the circuit formation process can be avoided. In view of the above, peel strength is measured using the following steps to evaluate the adhesion.
[0196] (Sample preparation for peel strength testing)
[0197] Metallized resin films (double-sided copper-clad laminates) made from the resin films obtained in the examples and comparative examples were used to prepare peel strength test samples with no copper on the back side and peel strength test samples with copper on the back side. For each peel strength test sample, the initial peel strength, peel strength after high-temperature heat treatment, and heat-resistant peel strength were measured.
[0198] (Method 1 - No copper backing)
[0199] The copper layer on a single surface of the double-sided copper-clad laminate was completely removed by etching. For the remaining single-sided copper layer, a 5mm wide copper pattern was created using an etching method with masking tape. The initial peel strength, peel strength after high-temperature heat treatment, and heat-resistant peel strength were determined according to the steps shown below.
[0200] "Initial Peel Strength - No Back Copper": After pattern etching, wipe away water droplets from both sides of the copper-clad laminate and remove the masking tape, then immediately measure the peel strength. Evaluate the adhesion of the two-sided copper-clad laminate in a state where neither drying nor high-temperature heating is performed, i.e., immediately after chemical plating.
[0201] "Peel strength after high-temperature heat treatment - no back copper"; After pattern etching, water droplets were wiped off the copper-clad laminates on both sides, the masking tape was removed, and the laminates were dried at 50°C for 10 minutes. Next, the copper-clad laminates were placed in a heat resistance test environment at 180°C for 15 minutes, and the peel strength was measured. This was performed to confirm the effect of high-temperature treatment on adhesion.
[0202] "Heat-resistant peel strength - no back copper"; After pattern etching, water droplets were wiped off the copper-clad laminates on both sides, the masking tape was removed, and the laminates were dried at 50°C for 10 minutes. Then, the copper-clad laminates were placed in a heat resistance test environment at 150°C for 168 hours, and the peel strength was measured. This was performed to evaluate heat resistance.
[0203] (Form 2 - with copper on the back)
[0204] For the copper layer on one side of a double-sided copper-clad laminate, a 5mm wide copper pattern was created using an etching method with masking tape to produce an evaluation pattern showing the entire back side covered with copper. Initial peel strength, peel strength after high-temperature heat treatment, and heat-resistant peel strength were measured using the following steps.
[0205] "Initial Peel Strength - With Back Copper"; After pattern etching, water droplets were wiped away from both sides of the copper-clad laminate, and the masking tape was removed. The peel strength was measured immediately afterward. This was an evaluation of the adhesion of the two-sided copper-clad laminate after chemical plating was performed without drying or high-temperature heating.
[0206] "Peel strength after high-temperature heat treatment - with copper back side"; After pattern etching, water droplets were wiped off the copper-clad laminates on both sides, the masking tape was removed, and the laminates were dried at 50°C for 10 minutes. Next, the copper-clad laminates were placed in a heat resistance test environment at 180°C for 15 minutes, and the peel strength was measured. This was performed to confirm the effect of high-temperature treatment on adhesion.
[0207] "Heat-resistant peel strength - with copper backing"; After pattern etching, water droplets were wiped off the copper-clad laminates on both sides, the masking tape was removed, and the laminates were dried at 50°C for 10 minutes. Then, the copper-clad laminates were placed in a heat resistance test environment at 150°C for 168 hours, and the peel strength was measured. This was performed to evaluate heat resistance.
[0208] (Peel strength test)
[0209] For a double-sided copper-clad laminate, the aforementioned six peel strength tests were performed. The peel strength was measured by peeling at a crosshead speed of 50 mm / min and a peel angle of 180°, and the load was determined.
[0210] <Moisture-absorbing welding thermal properties>
[0211] The evaluation double-sided copper-clad laminate obtained in the examples and comparative examples was cut into 3.5 cm square pieces. Next, for each 3.5 cm square evaluation double-sided copper-clad laminate, one side (conveniently referred to as side A) had a 2.5 cm square copper foil layer remaining in the center of the sample, while the opposite side (conveniently referred to as side B) had a copper foil layer remaining on the entire side. Excess copper foil was removed by etching, resulting in 15 samples. The obtained samples were placed under a humidified condition of 40°C and 90% RH for 96 hours for moisture absorption. After moisture absorption, five samples were immersed in a solder bath at 260°C, 280°C, or 300°C for 10 seconds. That is, five samples were used under one temperature condition. For the samples after solder immersion, the copper foil layer on side B was completely removed by etching, and the appearance of the overlapping copper foil area was observed. Any whitening, swelling, or peeling of the copper foil layer was considered a change in appearance. The following conditions are rated as follows: ○ (Good) if all five samples show no change in appearance at 300℃; △ (Acceptable) if any one or more of the five samples show a change in appearance at 300℃ but no change at 260℃; and × (Poor) if any one or more of the five samples show a change in appearance at 260℃.
[0212] <Surface Roughness Ra>
[0213] The copper layers of the double-sided copper-clad laminate obtained in the examples and comparative examples were removed by etching. The surface roughness (Ra) of the exposed resin film was measured according to JIS C 0601-2001 using a scanning probe microscope (SPM, Bruker AXS Dimming Icon).
[0214] (Synthesis Example 1; Synthesis of the polyimide precursor of layer A)
[0215] In a 2000 ml glass flask, 322.3 g of N,N-dimethylformamide (hereinafter also called DMF) and 33.9 g of 1,3-bis(4-aminophenoxy)benzene (hereinafter sometimes called TPE-R) were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 33.6 g of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (hereinafter sometimes called BPDA) was added, and the solution was stirred at 25°C for 1 hour. A separate solution (hereinafter sometimes called BPDA solution (1)) containing 0.51 g of BPDA dissolved in 9.7 g of DMF was prepared. While monitoring the viscosity, BPDA solution (1) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BPDA solution (1) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution, which serves as a precursor for polyimide, is obtained.
[0216] (Synthesis Example 2; Synthesis of the polyimide precursor of layer A)
[0217] In a 2000 ml glass flask, 321.4 g of N,N-dimethylformamide (hereinafter, sometimes referred to as DMF), 12.5 g of 4,4'-diaminodiphenyl ether (hereinafter, sometimes referred to as ODA), and 18.3 g of TPE-R were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 36.4 g of BPDA was added, and the solution was stirred at 25°C for 1 hour. A separate solution (hereinafter, sometimes referred to as BPDA solution (2)) containing 0.55 g of BPDA dissolved in 10.5 g of DMF was prepared. While monitoring the viscosity, BPDA solution (2) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BPDA solution (2) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0218] (Synthesis Example 3; Synthesis of the polyimide precursor of layer A)
[0219] In a 2000 ml glass flask, 321.8 g of N,N-dimethylformamide (hereinafter also called DMF), 24.7 g of TPE-R, and 7.6 g of 2,2'-dimethylbenzidine (hereinafter sometimes called m-TB) were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 35.0 g of BPDA was added, and the solution was stirred at 25°C for 1 hour. Separately, a solution containing 0.53 g of BPDA dissolved in 10.1 g of DMF (hereinafter sometimes called BPDA solution (3)) was prepared. While monitoring the viscosity, BPDA solution (3) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BPDA solution (3) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0220] (Synthesis Example 4; Synthesis of the polyimide precursor of layer A)
[0221] In a 2000 ml glass flask, 321.9 g of N,N-dimethylformamide (hereinafter also called DMF) and 35.0 g of TPE-R were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 6.5 g of pyromellitic dianhydride (hereinafter sometimes called PMDA) and 25.9 g of BPDA were added, and the solution in the flask was stirred at 25°C for 1 hour. A separate solution (hereinafter sometimes called BPDA solution (4)) containing 0.52 g of BPDA dissolved in 10.0 g of DMF was prepared. While monitoring the viscosity, BPDA solution (4) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BPDA solution (4) and the stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0222] (Synthesis Example 5; Synthesis of the polyimide precursor of layer A)
[0223] In a 2000 ml glass flask, 321.6 g of N,N-dimethylformamide (hereinafter also referred to as DMF) and 36.2 g of TPE-R were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 13.5 g of PMDA and 17.6 g of BPDA were added, and the solution was stirred at 25°C for 1 hour. Separately, a solution containing 0.54 g of BPDA dissolved in 10.3 g of DMF (hereinafter sometimes referred to as BPDA solution (5)) was prepared. While monitoring the viscosity, BPDA solution (5) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BPDA solution (5) and the stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0224] (Synthesis Example 6; Synthesis of the polyimide precursor of layer A)
[0225] In a 2000 ml glass flask, 320.4 g of N,N-dimethylformamide (hereinafter also referred to as DMF) and 27.5 g of ODA were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 39.8 g of BPDA was added, and the solution was stirred at 25°C for 1 hour. Separately, a solution containing 0.60 g of BPDA dissolved in 11.5 g of DMF (hereinafter sometimes referred to as BPDA solution (6)) was prepared. While monitoring the viscosity, BPDA solution (6) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BPDA solution (6) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0226] (Synthesis Example 7; Synthesis of the polyimide precursor of layer A)
[0227] In a 2000 ml glass flask, add 321.6 g of N,N-dimethylformamide (hereinafter also called DMF), 25.2 g of 2,2'-bis{4-(4-aminophenoxy)phenyl}propane (hereinafter sometimes called BAPP), and 6.6 g of 1,4-diaminobenzene (hereinafter sometimes called p-PDA). Then, while stirring the solution in the flask under a nitrogen atmosphere, add 35.6 g of BPDA and stir the solution at 25°C for 1 hour. Separately prepare a solution containing 0.54 g of BPDA dissolved in 10.3 g of DMF (hereinafter sometimes called BPDA solution (7)). While monitoring the viscosity, slowly add BPDA solution (7) to the aforementioned reaction solution and stir the reaction solution in the flask. Stop adding BPDA solution (7) and stirring the reaction solution when the viscosity of the reaction solution reaches 1000 poise. Through the above operations, a polyamic acid solution, which serves as a precursor for polyimide, is obtained.
[0228] (Synthesis Example 8; Synthesis of the polyimide precursor of layer A)
[0229] In a 2000 ml glass flask, 319.0 g of N,N-dimethylformamide (hereinafter also called DMF), 14.6 g of ODA, and 7.9 g of p-PDA were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 44.7 g of 4,4'-oxydiphthalic dianhydride (hereinafter, sometimes referred to as ODPA) was added, and the solution was stirred at 25°C for 1 hour. A separate solution (hereinafter, sometimes referred to as ODPA solution (1)) containing 0.68 g of ODPA dissolved in 12.9 g of DMF was prepared. While monitoring the viscosity, ODPA solution (1) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of ODPA solution (1) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0230] (Synthesis Example 9; Synthesis of the polyimide precursor of layer A)
[0231] In a 2000 ml glass flask, 321.1 g of N,N-dimethylformamide (hereinafter also referred to as DMF) and 35.7 g of TPE-R were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 13.3 g of PMDA and 18.3 g of ODPA were added, and the solution was stirred at 25°C for 1 hour. Separately, a solution containing 0.56 g of ODPA dissolved in 10.8 g of DMF (hereinafter sometimes referred to as ODPA solution (2)) was prepared. While monitoring the viscosity, ODPA solution (2) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of ODPA solution (2) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0232] (Synthesis Example 10; Synthesis of the polyimide precursor of layer A)
[0233] In a 2000 ml glass flask, 321.7 g of N,N-dimethylformamide (hereinafter also called DMF), 12.2 g of ODA, and 22.5 g of 4,4'-bis(4-aminophenoxy)biphenyl (hereinafter sometimes called 4-APBP) were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 8.0 g of PMDA and 24.6 g of BPDA were added, and the solution was stirred at 25°C for 1 hour. A separate solution (hereinafter sometimes called BPDA solution (8)) containing 0.54 g of BPDA dissolved in 10.2 g of DMF was prepared. While monitoring the viscosity, BPDA solution (8) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BPDA solution (8) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0234] (Synthetic Example 11; Synthesis of the polyimide precursor of layer A)
[0235] In a 2000 ml glass flask, 323.9 g of N,N-dimethylformamide (hereinafter also referred to as DMF) and 39.6 g of BAPP were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 39.6 g of BPDA was added, and the solution was stirred at 25°C for 1 hour. Separately, a solution containing 0.42 g of BPDA dissolved in 8.0 g of DMF (hereinafter sometimes referred to as BPDA solution (9)) was prepared. While monitoring the viscosity, BPDA solution (9) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BPDA solution (9) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0236] (Synthesis Example 12; Synthesis of the polyimide precursor of layer A)
[0237] In a 2000 ml glass flask, 320.0 g of N,N-dimethylformamide (hereinafter also called DMF) and 26.0 g of ODA were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 41.3 g of 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride (hereinafter sometimes called BTDA) was added, and the solution in the flask was stirred at 25°C for 1 hour. A separate solution (hereinafter sometimes called BTDA solution (1)) containing 0.62 g of BTDA dissolved in 11.9 g of DMF was prepared. While monitoring the viscosity, BTDA solution (1) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BTDA solution (1) and the stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0238] (Synthetic Example 13; Synthesis of the polyimide precursor of layer A)
[0239] In a 2000 ml glass flask, 318.8 g of N,N-dimethylformamide (hereinafter also called DMF), 14.2 g of ODA, and 7.7 g of p-PDA were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 45.3 g of BTDA was added, and the solution was stirred at 25°C for 1 hour. Separately, a solution containing 0.68 g of BTDA dissolved in 13.1 g of DMF (hereinafter sometimes referred to as BTDA solution (2)) was prepared. While monitoring the viscosity, BTDA solution (2) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of BTDA solution (2) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0240] (Synthetic Example 14; Synthesis of the polyimide precursor of layer A)
[0241] In a 2000 ml glass flask, 11.7 g of N,N-dimethylformamide (hereinafter also referred to as DMF) and 26.6 g of ODA were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 40.7 g of ODPA was added, and the solution was stirred at 25°C for 1 hour. A separate solution containing 0.61 g of ODPA dissolved in 11.7 g of DMF (hereinafter sometimes referred to as ODPA solution (3)) was prepared. While monitoring the viscosity, ODPA solution (3) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of ODPA solution (3) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0242] (Synthesis Example 15; Synthesis of the polyimide precursor of layer A)
[0243] In a 2000 ml glass flask, 322.0 g of N,N-dimethylformamide (hereinafter also referred to as DMF) and 32.9 g of TPE-R were added. Then, while stirring the solution in the flask under a nitrogen atmosphere, 34.4 g of ODPA was added, and the solution was stirred at 25°C for 1 hour. Separately, a solution containing 0.52 g of ODPA dissolved in 9.9 g of DMF (hereinafter sometimes referred to as ODPA solution (4)) was prepared. While monitoring the viscosity, ODPA solution (4) was slowly added to the aforementioned reaction solution, and the reaction solution in the flask was stirred. The addition of ODPA solution (4) and stirring of the reaction solution were stopped when the viscosity of the reaction solution reached 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor was obtained.
[0244] (Synthesis Example 16; Synthesis of the polyimide precursor of layer A)
[0245] In a 2000 ml glass flask, add 321.3 g of N,N-dimethylformamide (hereinafter also referred to as DMF), 25.8 g of ODA, and 4.6 g of p-PDA. Then, while stirring the solution in the flask under a nitrogen atmosphere, add 36.9 g of PMDA and stir at 25°C for 1 hour. Separately prepare a solution containing 0.56 g of PMDA dissolved in 10.6 g of DMF (hereinafter sometimes referred to as PMDA solution). While monitoring the viscosity, slowly add the PMDA solution to the aforementioned reaction solution, stirring the reaction solution in the flask. Stop adding the PMDA solution and stirring the reaction solution when the viscosity of the reaction solution reaches 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor is obtained.
[0246] (Synthesis Example 17; Synthesis of the polyimide precursor of layer A)
[0247] In a 2000 ml glass flask, add 320.9 g of N,N-dimethylformamide (hereinafter, also called DMF), 10.4 g of ODA, and 18.7 g of KF-8010 manufactured by Shin-Etsu Chemical Industry Co., Ltd. Then, while stirring the solution in the flask under a nitrogen atmosphere, add 38.1 g of 4,4'-(4,4'-isopropylidenediphenoxy)bis(phthalic anhydride) (hereinafter, sometimes called BPADA), and stir the solution in the flask at 25°C for 1 hour. Separately prepare a solution containing 0.58 g of BPADA dissolved in 11.0 g of DMF (hereinafter, sometimes called BPADA solution). While monitoring the viscosity, slowly add the BPADA solution to the aforementioned reaction solution, stirring the reaction solution in the flask. Stop adding the BPADA solution and stirring the reaction solution when the viscosity of the reaction solution reaches 1000 poise. Through the above operations, a polyamic acid solution as a polyimide precursor is obtained. The chemical structural formula of KF-8010 manufactured by Shin-Etsu Chemical Industry Co., Ltd. is shown in general formula (1).
[0248]
[0249] (Formulation Example 1; Dispersion of gaseous metal oxide used in layer A)
[0250] 20g of AEROSIL R9200 manufactured by AEROSIL Corporation of Japan was mixed with 80g of DMF. The resulting mixture was stirred in a rotary blade homogenizer (rotary blade diameter of 20mm) at 10000rpm for 5 minutes to obtain a dispersion of gaseous metal oxide.
[0251] (Formulation Example 2; Dispersion of gaseous metal oxide used in layer A)
[0252] The AEROSIL R9200 manufactured by AEROSIL Co., Ltd. of Japan in Formulation Example 1 was replaced with AEROSIL R972 manufactured by AEROSIL Co., Ltd. of Japan. Otherwise, the same operation as in Formulation Example 1 was performed to obtain a dispersion of gaseous metal oxide.
[0253] (Formulation Example 3; Dispersion of gaseous metal oxide used in layer A)
[0254] The AEROSIL R9200 manufactured by AEROSIL Corporation of Japan in Formulation Example 1 was replaced with AEROSIL NX130 manufactured by AEROSIL Corporation of Japan. Otherwise, the same operation as in Formulation Example 1 was performed to obtain a dispersion of gaseous metal oxide.
[0255] (Formulation Example 4; Dispersion of gaseous metal oxide used in layer A)
[0256] The AEROSIL R9200 manufactured by AEROSIL Corporation of Japan in Formulation Example 1 was replaced with AEROSIL VP RS920 manufactured by AEROSIL Corporation of Japan. Otherwise, the same operation as in Formulation Example 1 was performed to obtain a dispersion of gaseous metal oxide.
[0257] The concentration of the gaseous metal oxide in the dispersions of gaseous metal oxides obtained in Examples 1-4 was 20 wt%.
[0258] (Formulation Example 5; Dispersion of gaseous metal oxide used in layer A)
[0259] 30g of DMF was mixed into 60g of an Admanano dispersion with a particle size of 10nm (solvent DMF, concentration 30 wt%) prepared by Admatechs Co., Ltd., to obtain the dispersion.
[0260] (Formulation Example 6; Dispersion of gaseous metal oxide used in layer A)
[0261] A dispersion of Admanano with a particle size of 50 nm (solvent DMF, concentration 20 wt%) prepared by Admatechs Co., Ltd. was used directly as the dispersion.
[0262] (Example 1)
[0263] 40g of the polyamic acid solution obtained in Synthesis Example 1 was mixed with 17g of the dispersion from Preparation Example 1. 40g of DMF and 2g of dimethylpyridine were further mixed into the resulting mixture to obtain layer A dispersion. This layer A dispersion was coated onto one side of a non-thermoplastic polyimide film (Apical FP, 17 μm thick, manufactured by Kaneka Corporation) to achieve a final layer A thickness of 4 μm on one side. The layer A dispersion was dried at 120°C for 2 minutes. The same process was then repeated on the remaining side. The non-thermoplastic polyimide film coated with layer A dispersion was then heated at 450°C for 12 seconds to imidize the polyamic acid in layer A, resulting in a resin film composed of layers A (containing polyimide resin and fumed metal oxide) / non-thermoplastic polyimide film / layer A. It should be noted that the non-thermoplastic polyimide film (Apical FP) corresponds to layer B. That is, in Example 1, layer B is formed from polyimide resin, specifically consisting only of a non-thermoplastic polyimide film. Furthermore, the coefficient of linear expansion of this Apical FP is 12 ppm / °C.
[0264] The aforementioned resin film was subjected to desmearing treatment, electroless copper plating, and electrolytic copper plating under the conditions shown in Table 1 to obtain a double-sided copper-clad laminate. Peel strength, resistance to moisture-absorbing soldering heat, and surface roughness Ra were evaluated. The composition and results are shown in Tables 4 to 7.
[0265] (Example 2)
[0266] The dispersion used in Example 1 was changed to the dispersion used in Example 2. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0267] (Example 3)
[0268] The dispersion used in Example 1 was changed to the dispersion used in Example 3. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0269] (Example 4)
[0270] The dispersion used in Example 1 was changed to the dispersion used in Example 4. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0271] (Comparative Example 1)
[0272] 40g of the polyamic acid solution obtained in Synthesis Example 1 was mixed with 40g of DMF and 2g of dimethylpyridine to obtain a mixture. The layer A dispersion used in Example 1 was replaced with the aforementioned mixture, and the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, which were then evaluated in the same manner. The initial peel strength did not show sufficient values for either the absence of back copper or the presence of back copper. Furthermore, the peel strength after high-temperature heat treatment showed good adhesion without back copper, but not sufficient values with back copper; the adhesion results differed depending on the presence or absence of back copper. The composition and results are shown in Tables 4 to 7.
[0273] (Example 5)
[0274] The amount of the dispersion from Formulation Example 2 used in Example 2 was changed to 3.4 g. Otherwise, the same procedures as in Example 2 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0275] (Example 6)
[0276] The amount of the dispersion from Formulation Example 2 used in Example 2 was changed to 6.8 g. Otherwise, the same procedures as in Example 2 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0277] (Example 7)
[0278] The amount of the dispersion from Formulation Example 2 used in Example 2 was changed to 10.2 g. Otherwise, the same procedures as in Example 2 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0279] (Example 8)
[0280] The amount of dispersion from Formulation Example 2 used in Example 2 was changed to 34g. Otherwise, the same procedures as in Example 2 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0281] (Example 9)
[0282] The amount of the dispersion from Formulation Example 3 used in Example 3 was changed to 3.4 g. Otherwise, the same procedures as in Example 3 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0283] (Example 10)
[0284] The amount of the dispersion from Formulation Example 3 used in Example 3 was changed to 6.8 g. Otherwise, the same procedures as in Example 3 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0285] (Example 11)
[0286] The amount of the dispersion from Formulation Example 3 used in Example 3 was changed to 10.2 g. Otherwise, the same procedures as in Example 3 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0287] (Example 12)
[0288] The amount of the dispersion used in Example 3 was changed to 34g, but the same procedures as in Example 3 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0289] (Example 13)
[0290] The amount of dispersion from Formulation Example 1 used in Example 1 was changed to 6.8 g. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0291] (Example 14)
[0292] The amount of the dispersion from Formulation Example 1 used in Example 1 was changed to 10.2 g. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0293] (Example 15)
[0294] The amount of dispersion from Formulation Example 1 used in Example 1 was changed to 34g. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0295] (Example 16)
[0296] The amount of dispersion from Formulation Example 1 used in Example 1 was changed to 51g, but otherwise the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0297] (Example 17)
[0298] The amount of dispersion from Formulation Example 4 used in Example 4 was changed to 6.8 g. Otherwise, the same procedures as in Example 4 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0299] (Example 18)
[0300] The amount of the dispersion used in Example 4 was changed to 10.2 g, but the same procedures as in Example 4 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0301] (Example 19)
[0302] The amount of dispersion from Formulation Example 4 used in Example 4 was changed to 34g. Otherwise, the same procedures as in Example 4 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0303] (Example 20)
[0304] The amount of dispersion from Formulation Example 4 used in Example 4 was changed to 51g. Otherwise, the same procedures as in Example 4 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0305] (Example 21)
[0306] In the fabrication of the double-sided copper-clad laminate of Example 1, the processing conditions listed in Table 1 were used, except that the drying process after electroless copper plating was changed to water droplet wiping, and the drying process after sulfuric acid copper plating was also changed to water droplet wiping. Otherwise, the same operations as in Example 1 were performed to obtain the double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7. In the metallized resin film (double-sided copper-clad laminate) of Example 21, the six peel strengths showed good values, similar to those in Example 1. That is, without heating after the electroless metallization layer formation process, the metal plating layer adhered well to the resin film.
[0307] (Example 22)
[0308] The polyamic acid solution used in Example 1 was changed to the polyamic acid solution of Example 2. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0309] (Example 23)
[0310] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 3. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0311] (Example 24)
[0312] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 4. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0313] (Example 25)
[0314] The polyamic acid solution used in Example 1 was changed to the polyamic acid solution of Example 5. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0315] (Example 26)
[0316] The polyamic acid solution used in Example 1 was changed to the polyamic acid solution of Example 6. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0317] (Example 27)
[0318] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 7. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0319] (Example 28)
[0320] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 8. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0321] (Example 29)
[0322] The polyamic acid solution used in Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 9. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The composition and results are shown in Tables 4 to 7.
[0323] (Example 30)
[0324] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 10. Otherwise, the same operation as in Example 1 was performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was performed. The composition and results are shown in Tables 4 to 7.
[0325] (Example 31)
[0326] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 11. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The moisture absorption soldering thermal performance was evaluated as Δ. The composition and results are shown in Tables 4 to 7.
[0327] (Example 32)
[0328] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 12. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The moisture absorption soldering thermal performance was evaluated as Δ. The composition and results are shown in Tables 4 to 7.
[0329] (Comparative Example 2)
[0330] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 13. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The moisture absorption soldering thermal performance was rated as ×. The composition and results are shown in Tables 4 to 7.
[0331] (Example 33)
[0332] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 14. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The moisture-absorbing soldering thermal performance was evaluated as Δ. The composition and results are shown in Tables 4 to 7.
[0333] (Example 34)
[0334] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 15. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The moisture absorption soldering thermal performance was evaluated as Δ. The composition and results are shown in Tables 4 to 7.
[0335] (Comparative Example 3)
[0336] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 16. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The moisture absorption soldering thermal performance was evaluated as ×. The composition and results are shown in Tables 4 to 7.
[0337] (Comparative Example 4)
[0338] The polyamic acid solution used in Example 1 of Synthesis Example 1 was changed to the polyamic acid solution of Synthesis Example 17. Otherwise, the same procedures as in Example 1 were performed to obtain a resin film and a double-sided copper-clad laminate, and the same evaluation was conducted. The polyimide resin of layer A contains an organosilicon backbone, posing a risk of contact failure and process contamination in electronic devices due to the volatilization of siloxane components from the main chain backbone. Furthermore, layer A has a large coefficient of linear expansion, and its resistance to hygroscopic soldering heat is rated as ×. It exhibits poor dimensional stability and is also soluble in organic solvents, resulting in poor resistance to organic solvents during the printed circuit board manufacturing process. The composition and results are shown in Tables 4 to 7.
[0339] (Comparative Example 5)
[0340] The polyamic acid solution from Synthesis Example 17 was transferred to a shallow dish coated with a fluorinated resin and heated under reduced pressure at 200°C and 665 Pa for 120 minutes in a vacuum oven to obtain a polyimide resin. The obtained polyimide resin was dissolved in a mixed solvent of dioxolane and toluene (mixing ratio = 50 wt% / 50 wt%) to obtain a 17 wt% polyimide solution. 20 g of AEROSIL R9200 (manufactured by AEROSIL Corporation of Japan) was separately mixed with 80 g of the aforementioned mixed solvent. The resulting mixture was stirred at 10,000 rpm for 5 minutes in a rotary blade homogenizer (rotary blade diameter 20 mm) to obtain a dispersion of fumed metal oxides. 40 g of the aforementioned polyimide solution was mixed with 17 g of the aforementioned fumed metal oxide dispersion to obtain a fumed metal oxide-dispersed polyimide solution (hereinafter also referred to as layer A solution). The solution A was applied to one side of a non-thermoplastic polyimide film (Apical FP, 17 micrometers thick, manufactured by Kaneka Corporation), resulting in a final single-sided layer thickness of 4 micrometers. The solution A was dried at 60°C for 5 minutes and then at 150°C for 5 minutes. The same steps were then repeated for the remaining side. This process yielded a resin film composed of layer A / non-thermoplastic polyimide film / layer A. The same procedure as in Example 1 was then performed to obtain a double-sided copper-clad laminate, which was evaluated in the same way. The polyimide resin of layer A contains a silicone backbone, posing a risk of contact obstruction and process contamination in electronic devices due to the volatilization of siloxane components from the main chain backbone. Furthermore, its resistance to hygroscopic soldering heat was rated as ×. Additionally, layer A has a high coefficient of linear expansion, poor dimensional stability, and is soluble in organic solvents, resulting in poor resistance to organic solvents during printed circuit board manufacturing. The composition and results are shown in Tables 4 to 7.
[0341] [Table 4]
[0342]
[0343] [Table 5]
[0344]
[0345] [Table 6]
[0346] (Table 6)
[0347]
[0348] [Table 7]
[0349] (Table 7)
[0350]
[0351] [Table 8]
[0352]
[0353] [Table 9]
[0354]
[0355] [Table 10]
[0356]
[0357] [Table 11]
[0358]
Claims
1. A resin film, characterized in that, At least one side of layer B, which is a heat-resistant resin film with a linear expansion coefficient of less than 20 ppm / ℃, is formed a layer A comprising polyimide resin and fumed oxide. The gaseous oxide is a gaseous metal oxide or a gaseous silicon dioxide. The linear expansion coefficient of the polyimide resin is above 30 ppm / ℃ and below 100 ppm / ℃. The gaseous oxide comprises a structure formed by the primary particle aggregation of gaseous oxides.
2. The resin film according to claim 1, characterized in that, The apparent specific gravity of the gaseous oxide is above 20 g / L and below 220 g / L.
3. The resin film according to claim 1, characterized in that, The amount of the gaseous oxide relative to 10 to 130 parts by weight of the compounding amount relative to 100 parts by weight of the polyimide resin precursor is 10 parts by weight to 130 parts by weight.
4. The resin film according to claim 1, characterized in that, The gaseous oxide is gaseous silicon dioxide.
5. The resin film according to claim 1, characterized in that, Layer A, which contains the polyimide resin and the fumed oxide, is obtained by imidizing a mixture of the polyimide resin precursor and the fumed oxide.
6. The resin film according to claim 1, characterized in that, The storage modulus of the polyimide resin at 300°C is 1×10⁻⁶. 8 Pa or above.
7. The resin film according to claim 1, characterized in that, The polyimide resin is a non-soluble polyimide resin.
8. The resin film according to claim 1, characterized in that, Layer B comprises polyimide resin.
9. A metallized resin film having a chemically plated metal layer formed on the surface of layer A of the resin film of claim 1.
10. The metallized resin film according to claim 9, characterized in that, The electroless metal plating is electroless copper plating.
11. The metallized resin film according to claim 9, characterized in that, The surface roughness Ra of the resin film exposed by etching to remove the chemically plated metal layer of the metallized resin film is less than 200 nanometers.
12. The metallized resin film according to claim 9, characterized in that, After the chemically plated metal layer is formed in the metallized resin film, it exhibits a peel strength of 5 N / cm or higher without heat treatment at 150°C or higher.
13. A printed circuit board that uses the resin film of any one of claims 1 to 8 or the metallized resin film of any one of claims 9 to 12.
14. The printed circuit board according to claim 13, which is capable of transmitting electrical signals in the GHz band.
15. A method for manufacturing a resin film, characterized in that, The resin film has a layer A comprising polyimide resin and fumed oxide formed on at least one side of layer B, which is a heat-resistant resin film with a linear expansion coefficient of less than 20 ppm / ℃. The gaseous oxide is a gaseous metal oxide or a gaseous silicon dioxide. The linear expansion coefficient of the polyimide resin is above 30 ppm / ℃ and below 100 ppm / ℃. Layer A, comprising the polyimide resin and the fumed oxide, is obtained by mixing a polyamic acid solution, which is a precursor of the polyimide resin, with the fumed oxide, and then imidizing the resulting fumed oxide-dispersed polyamic acid solution. The gaseous oxide comprises a structure formed by the primary particle aggregation of gaseous oxides.
16. The method for manufacturing a resin film according to claim 15, characterized in that, The fumed oxide dispersed polyamic acid solution is coated onto layer B formed from the heat-resistant resin film, and the fumed oxide dispersed polyamic acid solution is dried and imidized.
17. The method for manufacturing a resin film according to claim 15, characterized in that, The fumed oxide dispersed polyamic acid solution is co-extruded with the precursor solution of layer B formed from the heat-resistant resin film, and the fumed oxide dispersed polyamic acid solution and the precursor solution are dried and imidized.
18. A method for manufacturing a resin film, characterized in that, The resin film has a layer A comprising polyimide resin and fumed oxide formed on at least one side of layer B, which is a heat-resistant resin film with a linear expansion coefficient of less than 20 ppm / ℃. The gaseous oxide is a gaseous metal oxide or a gaseous silicon dioxide. Layer A, comprising the polyimide resin and the fumed oxide, is obtained by mixing a polyamic acid solution, which serves as a precursor to the polyimide resin, with the fumed oxide, and then imidizing the resulting fumed oxide-dispersed polyamic acid solution. The fumed oxide is mixed in a proportion of 10 to 130 parts by weight relative to 100 parts by weight of the polyimide resin precursor. The gaseous oxide comprises a structure formed by the primary particle aggregation of gaseous oxides.
19. The method for manufacturing a resin film according to claim 18, characterized in that, When the apparent specific gravity of the fumed oxide is 70 g / L or more and 250 g / L or less, the proportion of the fumed oxide relative to 100 parts by weight of the precursor of the polyimide resin is 15 parts by weight or more and 120 parts by weight or less.
20. The method for manufacturing a resin film according to claim 18, characterized in that, When the apparent specific gravity of the fumed oxide is 20 g / L or more and 70 g / L or less, the proportion of the fumed oxide relative to 100 parts by weight of the precursor of the polyimide resin is 15 parts by weight or more and 80 parts by weight or less.
Citation Information
Patent Citations
JP1975037168A
Method of producing ultrathin copper foil with carrier, and ultrathin copper foil with carrier produced by the production method
JP2005076091A
Polyimide metal laminate
CN1592540A